SEALING FILM COMPOSITION FOR SEALING MICROCELLS IN ELECTRO-OPTICAL DEVICES - Patent application

JP2024546061AActive Publication Date: 2024-12-17E INK CORP
View PDF 30 Cites 0 Cited by

Patent Information

Application Number
JP2024529629
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-11-19
Filing Date
2022-11-14
Publication Date
2024-12-17
Estimated Expiration
2042-11-14

Smart Images

  • Figure 2024546061000001_ABST
    Figure 2024546061000001_ABST
Patent Text Reader

Abstract

The present invention is directed to an aqueous sealing composition comprising a polymer combination of poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer and polyurethane, a conductive filler, and a water-soluble ether in an aqueous carrier. The aqueous sealing composition can be used to form a sealing film in an electro-optical device having an electro-optical material layer disposed between two electrode layers, the device including (a) a plurality of microcells filled with charged particles and a non-polar fluid, and (b) a sealing film. The device exhibits good electro-optical performance.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Related Applications This application claims priority to U.S. Provisional Patent Application No. 63 / 281,345, filed November 19, 2021. Any patents, published applications or other published documents referenced herein are incorporated by reference in their entirety.

[0002] FIELD OF THEINVENTION The present invention relates to a sealing film that can be used in electro-optical devices, such as electrophoretic displays. The sealing film comprises a poly(vinyl alcohol) homopolymer or a poly(vinyl alcohol-co-ethylene) copolymer, a polyurethane, a conductive filler, and a water-soluble ether. The sealing film can be formed by curing or drying an aqueous sealing composition. [Background technology]

[0003] 2. Background of the Invention The term "electro-optical," as applied to a material or display, is used herein in its conventional sense in the imaging arts to refer to a material having first and second display states that differ in at least one optical property, and that changes from its first display state to its second display state upon application of an electric field to the material. The optical property is typically color as perceived by the human eye, but may also be another optical property, such as light transmission, reflectance, emission, or, in the case of displays intended to be machine-readable, pseudocolor in the sense of a change in reflectance of electromagnetic wavelengths outside the visible range.

[0004] The terms "bistable" and "bi-stable" are used herein in their conventional sense in the art to refer to displays containing display elements having first and second display states differing in at least one optical property, such that any given element is driven to assume either its first or second display state with an addressing pulse of finite duration, and the state persists after the addressing pulse has ended for at least several times, e.g., at least four times, the minimum duration of the addressing pulse required to change the state of the display element. In U.S. Pat. No. 7,170,670 it is shown that some particle-based electrophoretic displays capable of gray scale are stable not only in their extreme black and white states, but also in their intermediate gray states, and the same is true for some other types of electro-optical devices. Displays of this type are properly referred to as "multi-stable" rather than bistable, but for convenience the term "bistable" may be used herein to cover both bistable and multi-stable displays.

[0005] One type of electro-optical device that has been the subject of intense research and development over the years is the particle-based electrophoretic display, in which a plurality of charged particles move through a fluid under the influence of an electric field. Electrophoretic displays can have attributes of good brightness and contrast, wide viewing angles, state bistability, and low power consumption when compared to liquid crystal displays.

[0006] Numerous patents and applications assigned to or in the name of Massachusetts Institute of Technology (MIT), E Ink Corporation, E Ink California, LLC and affiliates describe various techniques used in encapsulated and microcell electrophoretic media, as well as other electro-optical media. Encapsulated electrophoretic media includes a number of small capsules, each of which includes an internal phase that contains electrophoretically mobile particles in a fluid medium, and a capsule wall surrounding the internal phase. Typically, the capsules are themselves held in a polymer binder to form a coherent layer located between two electrodes. In microcell electrophoretic displays, the charged particles and fluid are not encapsulated in microcapsules, but instead are held in a carrier medium, typically a plurality of cavities formed in a polymer film.

[0007] The technologies described in these patents and applications include:

[0008] (a) Electrophoretic particles, fluids and fluid additives, see, e.g., U.S. Pat. Nos. 7,002,728 and 7,679,814.

[0009] (b) Capsules, binders and encapsulation processes, see, e.g., U.S. Pat. Nos. 6,922,276 and 7,411,719.

[0010] (c) Microcell structures, wall materials, and methods of forming the microcells, see, for example, US Pat. Nos. 7,072,095 and 9,279,906.

[0011] (d) Methods for filling and sealing microcells, see, e.g., U.S. Pat. Nos. 7,144,942, 7,005.468, and 7,715,088, and U.S. Patent Application Publication Nos. 2004-0120024 and 2004-0219306.

[0012] (e) Films and subassemblies containing electro-optical materials, see, for example, US Pat. Nos. 6,982,178 and 7,839,564.

[0013] (f) Backplanes, adhesive layers and other auxiliary layers and methods used in displays, see, for example, US Pat. Nos. 7,116,318 and 7,535,624.

[0014] (g) Color formation and color adjustment, see, for example, U.S. Pat. Nos. 7,075,502 and 7,839,564.

[0015] (h) Methods for driving displays, see, for example, US Pat. Nos. 7,012,600 and 7,453,445.

[0016] (i) Display applications, see, for example, US Pat. Nos. 7,312,784 and 8,009,348.

[0017] (j) Non-electrophoretic displays, and non-display applications of encapsulation and microcell technology, as described in U.S. Pat. No. 6,241,921 and U.S. Patent Application Publication No. 2015 / 0277160, see, e.g., U.S. Pat. No. 7,615,325, and U.S. Patent Application Publication Nos. 2015 / 0005720 and 2016 / 0012710.

[0018] The contents of all of the above references are incorporated herein by reference in their entirety. Structures with a plurality of sealed microcells containing a dispersion of charged pigment particles in a non-polar fluid are commercially used in electro-optical devices. Microcells are also known in the literature as microcavities or microcups. A typical method for making sealed microcell structures for electro-optical devices includes (a) fabricating a polymer sheet with a plurality of microcavities by microembossing, each microcavity having an opening; (b) filling the microcavities with an electrophoretic medium, which is a dispersion containing charged pigment particles in a non-polar fluid; and (c) sealing the microcavities with an aqueous sealing composition to form a sealing film. The sealed microcavities containing the electrophoretic medium form the electro-optical material layer of the device. The electro-optical material layer is disposed between a front electrode and a back electrode. Application of an electric field across the electrophoretic medium by these electrodes causes the pigment particles to migrate through the electrophoretic medium to produce an image. The sealing film plays an important role for the function and performance of the device. First, since the sealing film contacts the electrophoretic medium and seals it inside the microcavity, the sealing layer must (1) be practically insoluble in the non-polar fluid of the electrophoretic medium, and (2) be a good barrier to the non-polar fluid so that the non-polar fluid does not diffuse out of the microcell during the device's lifetime. Second, the sealing film must not absorb significant amounts of moisture from the environment, i.e., it must not allow environmental moisture to enter the electrophoretic medium of the device. Such moisture can have a negative effect on the electro-optical performance of the device. The sealing film should have an optimal volume resistivity that is mechanically resilient and remains practically constant over time during the useful life of the device. Poor barrier properties of the sealing film to non-polar fluids will result in a reduction of fluid from the electrophoretic medium and sagging of the sealing film. Finally, the conductive properties of the sealing film are important because electrical potentials are applied throughout the device and are transmitted through the sealing film, among other components.The technical problem of providing an aqueous sealing composition that forms a sealing film having these characteristics is difficult because different formulation strategies may be required for different purposes. For example, barrier properties against non-polar fluids typically require more hydrophilic components, while such components absorb more moisture from the environment. If the sealing film has low electrical conductivity, the operation of the device requires increased power consumption, while too high conductivity may cause poor image quality due to blooming. Thus, there is a need for an aqueous sealing composition that forms a sealing film optimized for improved barrier against non-polar fluids, reduced moisture absorption, and improved electro-optical performance. The present inventors have found that a sealing film composition that includes a combination of poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer, polyurethane, conductive carbon black, and water-soluble ether provides a sealing film with good electro-optical performance and excellent color. [Prior art documents] [Patent documents]

[0019] [Patent Document 1] U.S. Patent No. 7,170,670 [Patent Document 2] U.S. Patent No. 7,002,728 [Patent Document 3] U.S. Patent No. 7,679,814 [Patent Document 4] U.S. Patent No. 6,922,276 [Patent Document 5] U.S. Pat. No. 7,411,719 [Patent Document 6] U.S. Patent No. 7,072,095 [Patent Document 7] U.S. Pat. No. 9,279,906 [Patent Document 8] U.S. Patent No. 7,144,942 [Patent Document 9] U.S. Patent No. 7,005,468 [Patent Document 10] U.S. Patent No. 7,715,088 [Patent Document 11] US Patent Application Publication No. 2004 / 0120024 [Patent Document 12] US Patent Application Publication No. 2004 / 0219306 [Patent Document 13] U.S. Patent No. 6,982,178 [Patent Document 14] U.S. Pat. No. 7,839,564 [Patent Document 15] U.S. Patent No. 7,116,318 [Patent Document 16] U.S. Patent No. 7,535,624 [Patent Document 17] U.S. Patent No. 7,075,502 [Patent Document 18] U.S. Patent No. 7,012,600 [Patent Document 19] U.S. Patent No. 7,453,445 [Patent Document 20] U.S. Patent No. 7,312,784 [Patent Document 21] U.S. Pat. No. 8,009,348 [Patent Document 22] U.S. Patent No. 6,241,921 [Patent Document 23] US Patent Application Publication No. 2015 / 0277160 [Patent Document 24] U.S. Patent No. 7,615,325 [Patent Document 25] US Patent Application Publication No. 2015 / 0005720 [Patent Document 26] US Patent Application Publication No. 2016 / 0012710 Summary of the Invention [Means for solving the problem]

[0020] Summary of the Invention In one aspect, the present invention is directed to a seal film comprising: a water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer in a content of 15% to 60% by weight based on the weight of the seal film, the poly(vinyl alcohol) homopolymer having a degree of hydrolysis of 90% to 99.5%, and the poly(vinyl alcohol-co-ethylene) copolymer having a degree of hydrolysis of 90% to 99.5% and an ethylene content of less than 10%; a polyurethane in a content of 7% to 29% by weight based on the weight of the seal film; carbon black in a content of 5% to 70% by weight based on the weight of the seal film; and a water-soluble ether in a content of 0.5% to 25% by weight based on the weight of the seal film.

[0021] The poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer may have a number average molecular weight of 1,000 to 1,000,000 Daltons. The poly(vinyl alcohol) polymer or poly(vinyl alcohol-co-ethylene) copolymer may have a degree of hydrolysis of 92% to 99%. The polyurethane polymer may have a number average molecular weight of 1,000 to 2,000,000 Daltons. The polyurethane may be an ester polyurethane, a polycarbonate polyurethane, or a combination thereof. The total surface energy of the sealing film may be lower than 60 mN / m. The interfacial tension between the water-soluble poly(vinyl alcohol) polymer or poly(vinyl alcohol-co-ethylene) copolymer and the polyurethane may be less than 2 mN / m. The sealing film may further include an organosilicone wetting agent.

[0022] The water-soluble ether has a molecular weight of 75 to 5,000 daltons and optionally contains a hydroxy group. The water-soluble ether is represented by Formula I, Formula II, or Formula III. [ka] Represented by [wherein n is 1 to 145, R1 is hydrogen, a methyl or ethyl group, R2, R3, R4, R5, R6, and R7 are independently selected from the group consisting of hydrogen, a straight or branched alkyl group containing 1 carbon atom to 6 carbon atoms, phenyl, and a benzyl group, and formula I contains at least one ether functional group, formula II contains at least one ether functional group, and formula III contains at least one ether functional group]. For formula I, n can be 1 to 10. The seal film is 10 8 ~10 10 It may have a volume resistivity of ohm.cm.

[0023] In another aspect, the invention is directed to an electrophoretic device including a conductive layer; a microcell layer including a plurality of microcells, each microcell including an opening, each microcell including an electrophoretic medium, the electrophoretic medium including charged particles in a non-polar carrier; a sealing film spanning the opening of each microcell; an adhesive layer; and an electrode layer. The seal film comprises a water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer in a content of 15% to 60% by weight based on the weight of the seal film, the poly(vinyl alcohol) homopolymer having a degree of hydrolysis of 90% to 99.5%, and the poly(vinyl alcohol-co-ethylene) copolymer having a degree of hydrolysis of 90% to 99.5% and an ethylene content of less than 10%; a polyurethane in a content of 7 to 29% by weight based on the weight of the seal film; carbon black in a content of 5% to 70% by weight based on the weight of the seal film; and a water-soluble ether in a content of 0.5% to 25% by weight based on the weight of the seal film, the water-soluble ether having a molecular weight of 70 to 5,000 daltons, and optionally including a hydroxyl-containing water-soluble ether. The electrophoretic medium may include at least three types of charged pigment particles, one type of charged particle having a color selected from the group consisting of blue, green, red, cyan, magenta, and yellow.

[0024] In yet another aspect, the present invention is directed to an aqueous sealing composition comprising: a water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer in a content of 14% to 55% by weight, based on the weight of the aqueous sealing composition excluding water, the poly(vinyl alcohol) homopolymer having a degree of hydrolysis of 90% to 99.5% and the poly(vinyl alcohol-co-ethylene) copolymer having a degree of hydrolysis of 90% to 99.5% and an ethylene content of less than 10%; a polyurethane in a content of 6% to 27% by weight, based on the weight of the aqueous sealing composition excluding water; carbon black in a content of 5% to 64% by weight, based on the weight of the aqueous sealing composition excluding water; a water-soluble ether in a content of 1.0% to 40% by weight, based on the weight of the aqueous sealing composition excluding water, the water-soluble ether having a molecular weight of 75 to 5,000 daltons and optionally containing a hydroxy group; and water in a content of 20% to 95% by weight, based on the weight of the aqueous sealing composition. The aqueous sealing composition may further include a crosslinking agent in a content of 0.1% to 8% by weight based on the weight of the aqueous sealing composition excluding water, the crosslinking agent being a polyisocyanate, a polyfunctional polycarbodiimide, a polyfunctional aziridine, a silane coupling agent, a boron / titanium / zirconium-based crosslinking agent, or melamine formaldehyde. The aqueous sealing composition may further include a rheology control agent in a content of 0.05% to 5% by weight based on the weight of the aqueous sealing composition excluding water. [Brief description of the drawings]

[0025] [Figure 1] FIG. 1 shows a side view of a multi-microcell structure prior to being filled and sealed.

[0026] [Diagram 2] FIG. 2 shows a side view of an example electro-optical device including a microcell structure.

[0027] [Diagram 3]FIG. 3 shows a side view of an example front plane laminate assembly that can be used to form an electro-optical device that includes a microcell structure.

[0028] [Figure 4] FIG. 4 shows a side view of an example of a dual release sheet that can be used to form an electro-optical device that includes a microcell structure.

[0029] [Diagram 5] FIG. 5 illustrates a method for fabricating a microcell using a roll-to-roll process.

[0030] [Figure 6-1] 6A and 6B detail the creation of a microcell using photolithographic exposure through a photomask of a conductor film coated with a thermoset precursor.

[0031] [Figure 6-2] Figures 6C and 6D detail an alternative embodiment of the fabrication of a microcell array using photolithography, in which a combination of top and bottom exposures is used to allow one horizontal partition wall to be cured by a top photomask exposure and another horizontal partition wall to be cured by a bottom exposure through an opaque base conductor film.

[0032] [Figure 7A] 7A-7D show the steps of filling and sealing the array of microcells. [Figure 7B] 7A-7D show the steps of filling and sealing the array of microcells. [Figure 7C] 7A-7D show the steps of filling and sealing the array of microcells. [Figure 7D] 7A-7D show the steps of filling and sealing the array of microcells.

[0033] [Figure 8-1] 8A-8D show various components constructed for the evaluation of the volume resistivity of the seal film.

[0034] [Figure 8-2] Figures 8A-8D show various components constructed for evaluation of the volume resistivity of the seal film, and Figure 8E shows the waveform used for evaluation of the volume resistivity of the seal film.

[0035] [Figure 9] FIG. 9 shows the electrical impedance spectroscopy results of the control and inventive sealing films.

[0036] [Figure 10] FIG. 10 shows the structure of the electro-optical device used for evaluation of the electro-optical performance of the water-based sealing composition.

[0037] [Figure 11] FIG. 11 shows the waveforms used to determine the color gamut of the inventive and control electro-optic devices.

[0038] [Figure 12] FIG. 12 shows a side view of the electro-optical device structure used to evaluate the barrier properties of the aqueous sealing composition.

[0039] [Figure 13A] 13A-13D show microscopic images of the microcells evaluated for barrier properties. [Figure 13B] 13A-13D show microscopic images of the microcells evaluated for barrier properties. [Figure 13C] 13A-13D show microscopic images of the microcells evaluated for barrier properties. [Figure 13D] 13A to 13D show microscopic images of microcells evaluated for barrier properties.

[0040] [Figure 14] FIG. 14 shows microscope images of polymeric sealing films containing combinations of poly(vinyl alcohol-co-ethylene) copolymer and polyurethane having various interfacial tensions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0041] Detailed Description of the Invention As used herein, "molecular weight" refers to the weight average molecular weight of a compound, unless otherwise stated. Molecular weight is measured using gel permeation chromatography, an industry standard method.

[0042] The degree of hydrolysis of a poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer is the ratio of the moles of vinyl alcohol groups to the sum of the moles of vinyl alcohol groups and the moles of vinyl acetate groups in the polymer. Thus, for the simplified polyvinyl alcohol formula example provided below (Formula IV), the degree of hydrolysis is calculated according to Equation 1: Degree of hydrolysis=100×p / (p+q) Equation 1 Typically, manufacturers of polyvinyl alcohol report the degree of hydrolysis of their products. This parameter affects important physical properties of the polymer, such as the water solubility of the polymer and the water resistance of the corresponding dry film. To determine the degree of hydrolysis of polyvinyl alcohol (homopolymer and copolymer), a titration method is used. Details of the method are described in JIS K 6726 method (Japanese Standards Association, 94th edition, October 20, 2017). [ka]

[0043] The terms "sealing film" and "sealing layer" are synonymous and are used interchangeably with respect to electro-optical devices.

[0044] The terms "adhesive film" and "adhesive layer" are synonymous and are used interchangeably with respect to electro-optical devices.

[0045] Unless otherwise stated, the disclosed contents of components of the sealing film are calculated as the weight % of the component relative to the weight of the sealing film excluding water.Unless otherwise stated, the disclosed contents of components of the aqueous sealing composition are calculated as the weight % of the component relative to the weight of the aqueous sealing composition excluding water.

[0046] A. Microcell Structure

[0047] 1 shows a side view of a structure of multiple microcells 100 prior to being filled and sealed. Each microcell includes a base 101, a partition wall 102, and an opening 103.

[0048] B. Structure of an electro-optical device including a microcell structure

[0049] FIG. 2 shows a side view of an example of an electro-optical device 200 including microcells. The example electro-optical device 200 includes a first light-transmissive electrode layer 210, a microcell layer 220, a sealing film 230, an adhesive layer 240, and a second electrode layer 250. The microcell layer includes a plurality of microcells defined by a bottom 221 and a partition wall 222. Each of the plurality of microcells contains an electrophoretic medium 225, the medium including charged particles in a non-polar fluid. The microcells are sealed with a sealing film 230, which spans the openings of the plurality of microcells. The second electrode layer 250 is connected to the sealing film 230 using an adhesive layer 240. The plurality of microcells sealed by the sealing layer 230 and containing the electrophoretic medium 225 constitute the electro-optical material layer of the electro-optical device 200. A source of electric field may connect the first light-transmissive electrode layer 210 with the second electrode layer 250. Application of an electric field across the electrophoretic material layer causes charged particles to move through the electrophoretic medium to create an image that can be viewed by an observer looking from the viewing side 215 of the electro-optic device 200. An optional primer layer (not shown in FIG. 2) may be disposed between the first light-transmissive electrode layer 210 and the plurality of microcells 222.

[0050] The example electro-optical device shown in FIG. 2 may be constructed by a front plane laminate 300 shown in FIG. 3. The front plane laminate 300 includes a first light-transmissive electrode layer 310, a microcell layer 320 including a plurality of microcells 325, a sealing film 330, an adhesive layer 340, and a release sheet 360. Each microcell of the plurality of microcells contains an electrophoretic medium 325, the medium including charged particles in a non-polar fluid. The microcells 325 are sealed with a sealing film 330, which spans the openings of the plurality of microcells. The release sheet 360 is connected to the sealing film 330 using an adhesive layer 340. Removal of the release sheet 360 exposes a surface of the adhesive layer 340, which may be connected onto a second electrode layer to form an electro-optical device. An optional primer layer (not shown in FIG. 3) may be disposed between the first light-transmissive electrode layer 310 and the plurality of microcells 330.

[0051] The example of the electro-optical device shown in FIG. 2 may also be constructed with a dual release sheet 400 shown in FIG. 4. The dual release sheet 400 includes a first release sheet 480, a first adhesive layer 470, a microcell layer 420 including a plurality of microcells 425, a sealing film 430, a second adhesive layer 440, and a second release sheet 460. Each of the plurality of microcells contains an electrophoretic medium 425, which includes charged particles in a non-polar fluid. The microcells are sealed with a sealing film 430, which spans the openings of the plurality of microcells. The first release sheet 480 is connected to the microcell layer 420 with a first adhesive layer 470. The second release sheet 460 is connected to the sealing film 430 with a second adhesive layer 440. Removal of the first release sheet 480 exposes the surface of the first adhesive layer 470, which may be connected onto a first light-transmitting electrode layer. Removal of the second release sheet 460 exposes a surface of the second adhesive layer 440, which may be connected onto a second electrode layer to form an electro-optical device. An optional primer layer (not shown in FIG. 4) may be disposed between the first adhesive layer 470 and the microcell layer 430.

[0052] C. Formation of Microcell Structure

[0053] Techniques for constructing microcells. Microcells can be formed in either a batch-wise process or a continuous roll-to-roll process as disclosed in U.S. Pat. No. 6,933,098. The latter provides a continuous, low-cost, high-throughput manufacturing technique for generating compartments for use in a variety of applications, including delivery of beneficial agents and electrophoretic displays. Microcell arrays suitable for use with the present invention can be created using microembossing, as shown in FIG. 5. The male mold (500) can be placed either above the web 504 or below the web 504 (not shown). However, alternative arrangements are possible. See, for example, U.S. Pat. No. 7,715,088, which is incorporated herein by reference in its entirety. The conductive substrate can be constructed by forming a conductor film 501 on a polymer substrate that will become the backing layer for the device. A composition 502 containing a thermoplastic, thermoset, or precursors thereof is then coated onto the conductor film. The thermoplastic or thermoset precursor layer is embossed by a male mold in the form of a roller, plate or belt at a temperature above the glass transition temperature of the thermoplastic or thermoset precursor layer.

[0054] The thermoplastic or thermosetting precursors for the preparation of the microcells can be multifunctional acrylates or methacrylates, vinyl ethers, epoxides, and their oligomers or polymers, etc. The combination of multifunctional epoxides and multifunctional acrylates is also very useful for achieving desirable physical-mechanical properties. Crosslinkable oligomers that impart flexibility, such as urethane acrylates or polyester acrylates, can be added to improve the bending resistance of the embossed microcells. The composition may contain polymers, oligomers, monomers and additives, or may contain only oligomers, monomers and additives. The glass transition temperature (T g ) is typically in the range of about -70°C to about 150°C, or about -20°C to about 50°C. The microembossing process typicallyg A heated male mold, or a heated housing substrate against which the mold exerts pressure, can be used to control the temperature and pressure of the microembossing process.

[0055] As shown in FIG. 5, the mold is demolded while or after the precursor layer is cured to reveal an array of microcells 503. The curing of the precursor layer can be achieved by cooling, solvent evaporation, cross-linking by radiation, heat or moisture. If the curing of the thermosetting material precursor is achieved by UV radiation, the UV can be emitted from the bottom or top of the web onto the transparent conductor film, as shown in the two figures. Alternatively, a UV lamp can be placed inside the mold. In this case, the mold must be transparent to allow the UV light to be emitted through the pre-patterned male mold onto the thermosetting material precursor layer. The male mold can be prepared by any suitable method, for example, a diamond turning process or a photoresist process, followed by either etching or electroplating. The master template for the male mold can be manufactured by any suitable method, for example, electroplating. In electroplating, a glass base is sputtered with a thin layer of a seed metal, such as chrome inconel (typically 3000 Å). The mold is then coated with a layer of photoresist and exposed to UV. A mask is placed between the UV and a layer of photoresist. The exposed areas of the photoresist are hardened. The unexposed areas are then removed by washing with a suitable solvent. The remaining hardened photoresist is dried and a thin layer of seed metal is sputtered again. The master is then ready for electroforming. A typical material used for electroforming is nickel cobalt. Alternatively, the master can be made from nickel by electroforming or electroless nickel deposition. The floor of the mold is typically between about 50 and 400 microns. The master can also be made using other microengineering techniques including e-beam writing, dry etching, chemical etching, laser writing or laser interference as described in "Replication techniques for micro-optics", SPIE Proc. Vol. 3099, pp. 76-82 (1997). Alternatively, the mold can be made using plastic, ceramic or metal by photomachining.

[0056] Prior to applying the UV-curable resin composition, the mold may be treated with a release agent to aid in the demolding process. The UV-curable resin may be degassed prior to dispensing and may contain a solvent if necessary. The solvent, if present, evaporates easily. The UV-curable resin is dispensed by any suitable method, such as coating, dipping, pouring, etc., to cover the male mold. The dispensing device may be moving or stationary. The conductor film is superimposed on the UV-curable resin. If necessary, pressure may be applied to ensure proper bonding between the resin and the plastic and to control the thickness of the floor of the microcell. Pressure may be applied using laminating rollers, vacuum forming, compression devices, or any other similar means. If the male mold is metallic and opaque, the plastic substrate is typically transparent to the actinic radiation used to cure the resin. Conversely, the male mold may be transparent and the plastic substrate may not be transparent to the actinic radiation. To allow good transfer of the molded features onto the transfer sheet, the conductor film must have good adhesion to the UV-curable resin, which should have good release properties with respect to the mold surface.

[0057] Microcell arrays for the present invention typically include a preformed conductor film, such as indium tin oxide (ITO) conductor lines, although other conductive materials, such as silver or aluminum, may be used. The conductive layer may be backed by or integrated into a substrate, such as polyethylene terephthalate, polyethylene naphthalate, polyaramid, polyimide, polycycloolefin, polysulfone, epoxy, and composites thereof. The conductor film may be coated with a radiation-curable polymer precursor layer. The film and precursor layer are then imagewise exposed to radiation to form the microcell wall structure. After exposure, the precursor material is removed from the non-exposed areas, leaving the hardened microcell partition walls bonded to the conductor film / support web. Imagewise exposure may be accomplished by passing UV or other forms of radiation through a photomask to generate an exposure image or predetermined exposure pattern of the radiation-curable material coated on the conductor film. Although not generally necessary, the mask can be positioned and aligned relative to the conductor film, i.e., the ITO lines, such that the transparent mask portions align with the spaces between the ITO lines and the opaque mask portions align with the ITO material (intended for the cell bottom regions of the microcells).

[0058] Photolithography. Microcells can also be produced using photolithography. A photolithography process for fabricating a microcell array is shown in Figures 6A and 6B. As shown in Figures 6A and 6B, a microcell array 600 can be prepared by exposing a radiation curable material 601a, coated on a conductor electrode film 602 by known methods, to UV light (or alternatively other forms of radiation, e-beam, etc.) through a mask 606 to form partition walls 601b corresponding to the image projected through the mask 606. The base conductor film 602 is preferably mounted on a support substrate base web 603, which may include a plastic material.

[0059] In the photomask 606 of Figure 6A, the dark squares 604 represent the opaque areas and the spaces between the dark squares represent the transparent areas 605 of the mask 606. UV is emitted through the transparent areas 605 onto the radiation curable material 601a. ​​The exposure is preferably performed directly on the radiation curable material 601a, i.e., UV does not pass through to the substrate 603 or to the base conductors 602 (top exposure). For this reason, neither the substrate 603 nor the conductors 602 need to be transparent to the UV or other wavelengths of radiation used.

[0060] As shown in Figure 6B, the exposed areas 601b are cured. The unexposed areas (protected by the opaque areas 604 of the mask 606) are then removed by a suitable solvent or developer to form the microcells 607. The solvent or developer is selected from those commonly used to dissolve or reduce the viscosity of radiation curable materials, such as methyl ethyl ketone (MEK), toluene, acetone, isopropanol, etc. Preparation of the microcells can be accomplished similarly by placing a photomask under the conductor film / substrate support web, in which case UV light is emitted from the bottom through the photomask and the substrate needs to be transparent to the radiation.

[0061] Image-wise exposure. Yet another alternative method for the preparation of the microcell array of the present invention by image-wise exposure is shown in Figures 6C and 6D. When opaque conductor lines are used, the conductor lines can be used as a photomask for exposure from the bottom. Durable microcell partition walls are formed by further exposure from the top through a second photomask having opaque lines perpendicular to the conductor lines. Figure 6C shows the use of the exposure principle from both the top and bottom to produce the microcell array 610 of the present invention. The base conductor film 612 is opaque and patterned with lines. The radiation curable material 611a coated on the base conductor 612 and substrate 613 is exposed from the bottom through the conductor line pattern 612, which acts as the first photomask. The second exposure is performed from the "top" side through a second photomask 616 having a line pattern perpendicular to the conductor lines 612. The spaces 615 between the lines 614 are substantially transparent to UV light. In this process, the wall material 611b cures laterally from the bottom up and then cures vertically from the top down, together forming a complete microcell 617. The unexposed areas are then removed by a solvent or developer as previously described to reveal the microcell 617, as shown in Figure 6D.

[0062] The microcells can be constructed from thermoplastic elastomers that have good compatibility with the microcells and do not interact with the medium. Examples of useful thermoplastic elastomers include ABA and (AB)n type diblock, triblock, and multiblock copolymers, where A is styrene, α-methylstyrene, ethylene, propylene, or norbornene, and B is butadiene, isoprene, ethylene, propylene, butylene, dimethylsiloxane, or propylene sulfide, and A and B cannot be the same in the formula. The number n is ≧1, preferably 1-10. Particularly useful are diblock or triblock copolymers of styrene or ox-methylstyrene, such as SB (poly(styrene-b-butadiene)), SBS (poly(styrene-b-butadiene-b-styrene)), SIS (poly(styrene-b-isoprene-b-styrene)), SEBS (poly(styrene-b-ethylene / butylene-b-styrene (stylene))) poly(styrene-b-dimethylsiloxane-b-styrene), poly((α-methylstyrene-b-isoprene), poly(α-methylstyrene-b-isoprene-b-α-methylstyrene), poly(α-methylstyrene-b-propylene sulfide-b-α-methylstyrene), poly(α-methylstyrene-b-dimethylsiloxane-b-α-methylstyrene). Commercially available styrene block copolymers, such as the Kraton D and G series (Kraton Particularly useful are crystalline rubbers such as poly(ethylene-co-propylene-co-5-methylene-2-norbomene) or EPDM (ethylene-propylene-diene terpolymer) rubbers such as Vistalon 6505 (Exxon Mobil, Houston, Tex.) and grafted copolymers thereof.

[0063] The thermoplastic elastomer may be dissolved in a solvent or solvent mixture that is immiscible with the carrier in the microcell and exhibits a specific gravity lower than that of the carrier. Low surface tension solvents are preferred for the overcoating composition since they have better wetting properties than the microcell partition walls and their fluids. Solvents or solvent mixtures having a surface tension lower than 35 dynes / cm are preferred. Surface tensions lower than 30 dynes / cm are more preferred. Suitable solvents include alkanes (preferably C 6~12 Alkanes, such as heptane, octane or Isopar solvents from Exxon Chemical Company, nonane, decane and their isomers), cycloalkanes (preferably C 6~12 Cycloalkanes, such as cyclohexane and decalin, alkylbenzenes (preferably mono- or di-C 1~6 Alkylbenzenes, such as toluene, xylene, etc.), alkyl esters (preferably C 2~5 Alkyl esters, such as ethyl acetate, isobutyl acetate, etc.) and C 3~5 Included are alkyl alcohols (e.g., isopropanol, etc. and their isomers). Mixtures of alkyl benzenes and alkanes are particularly useful.

[0064] In addition to the polymer additive, the polymer mixture may contain a wetting agent (surfactant). Also, in order to improve the adhesion of the sealant to the microcell and provide a more flexible coating process, wetting agents (e.g., FC surfactants from 3M Company, Zonyl fluorosurfactants from DuPont, fluoroacrylates, fluoromethacrylates, fluoro-substituted long-chain alcohols, perfluoro-substituted long-chain carboxylic acids and their derivatives, and Silwet silicone surfactants from OSi, Greenwich, Conn.) may be included in the composition. Other ingredients are also very useful to enhance the physical and mechanical properties of the seal film by crosslinking or polymerization reactions during or after the overcoating process, including crosslinking agents (e.g., bisazides, such as 4,4'-diazidodiphenylmethane and 2,6-di-(4'-azidobenzal)-4-methylcyclohexanone), vulcanizing agents (e.g., 2-benzothiazolyl disulfide and tetramethylthiuram disulfide), multifunctional monomers or oligomers (e.g., hexanediol, diacrylates, trimethylolpropane, triacrylates, divinylbenzene, diallylphthalene), thermal initiators (e.g., dilauroyl peroxide, benzoyl peroxide) and photoinitiators (e.g., isopropylthioxanthone (ITX), Irgacure 651 and Irgacure 369 from Ciba-Geigy).

[0065] A microcell array, such as the array 700 shown in Figure 7A, may be prepared by any of the methods described above. As shown in the cross-sectional views of Figures 7A-7D, the microcell partition walls 702 extend upward from the microcell bottom 701 and the conductive layer 710 to form an open microcell. In one embodiment, the conductive layer 710 is formed on or at the microcell bottom 701. Although Figures 7A-7D show the conductive layer 710 extending continuously over the microcell bottom 701, it is also possible for the conductive layer 710 to extend continuously below or within the bottom 701 or to be interrupted by the microcell partition walls 702.

[0066] The microcells are then filled with an electrophoretic medium 725 containing charged particles in a non-polar fluid to form a plurality of filled microcells 770. The microcells may be filled using a variety of techniques. In some embodiments, blade coating may be used to fill the microcells to the depth of the microcell partition walls 702.

[0067] 7C, after filling, the microcells are sealed by applying an aqueous sealing composition to form sealed microcells 780 containing sealing film 730. In some embodiments, the sealing process may include exposure to heat, dry hot air, or UV radiation. The sealing film should have good barrier properties to the non-polar fluids of the electrophoretic medium 725.

[0068] In an alternative embodiment, various individual microcells can be filled with the desired mixture by using repeated photolithography. This process typically involves coating an array of empty microcells with a layer of photoresist acting as a positive type, selectively opening a certain number of microcells by imagewise exposing the positive type photoresist, subsequently developing the photoresist, filling the open microcells with the desired mixture, and sealing the filled microcells by a sealing process. These steps can be repeated to create sealed microcells filled with other mixtures. This procedure allows the formation of large sheets of microcells having the desired ratios or concentrations of mixtures.

[0069] Sealing of the filled microcells can be accomplished in several ways. One approach involves mixing an aqueous sealing composition with an electrophoretic medium composition. The aqueous sealing composition can be immiscible with the electrophoretic composition, and preferably has a lower specific gravity than that of the electrophoretic medium composition. The two compositions, the sealing composition and the electrophoretic medium composition, are thoroughly mixed and immediately coated onto a number of microcells using a precise coating mechanism, such as a Mayer bar, gravure, doctor blade, slot coating, or slit coating. Excess fluid is scraped off by a wiper blade or similar device. A small amount of a weak solvent or solvent mixture, such as isopropanol, methanol, or an aqueous solution thereof, can be used to clean the fluid remaining on the top surface of the partition wall of the microcell. The aqueous sealing composition is then separated from the electrophoretic medium composition and floats on top of the liquid composition of the electrophoretic medium. Alternatively, after the mixture of electrophoretic medium composition and aqueous sealing composition is filled into the microcell, a substrate can be laminated on top to control the metering of the mixture of compositions and promote phase separation of the aqueous sealing composition from the electrophoretic medium composition to form a uniform sealing film. The substrate used can be a functional substrate in the final structure or a sacrifice substrate, such as a release substrate, that can be removed later. The sealing film is then formed by curing the aqueous sealing composition in situ (i.e., when in contact with the electrophoretic medium composition). Curing of the aqueous sealing composition can be accomplished by UV or other forms of radiation, such as visible light, IR, or electron beam. Alternatively, when a heat or moisture curable aqueous sealing composition is used, heat or moisture can also be used to cure the aqueous sealing composition.

[0070] In the second approach, the electrophoretic medium composition may be filled into the microcells first, and then the aqueous sealing composition is overcoated onto the filled microcells. Overcoating may be accomplished by conventional coating and printing processes, such as blanket coating, inkjet printing, or other printing processes. In this approach, the sealing film is formed in situ by curing the aqueous sealing composition by solvent evaporation, radiation, heat, moisture, or interfacial reaction. Interfacial polymerization followed by UV curing is beneficial to the sealing process. Intermixing of the electrophoretic medium composition and the sealing overcoat is significantly suppressed by the formation of a thin barrier layer at the interface by interfacial polymerization. The sealing is then completed by a post-curing step, for example by UV radiation. The degree of intermixing may be further reduced by using an aqueous sealing composition having a specific gravity lower than that of the electrophoretic medium composition. Volatile organic solvents may be used to adjust the viscosity and thickness of the sealing overcoat. The rheology of the aqueous sealing composition may be tailored for optimal sealability and coatability. If a volatile solvent is used in the overcoat, it is preferred that the volatile solvent be immiscible with the solvent in the electrophoretic medium composition.

[0071] After the microcells are filled and sealed, the sealed microcell array can be laminated with a second electrode layer 750 including multiple electrodes, as shown in FIG. 7D. The second electrode layer 750 is bonded onto the sealing film 730 to form an electro-optical device 790, as shown in FIG. 7D. An adhesive can be used to bond the second electrode layer 750 onto the sealing film 730. The adhesive layer is not shown in FIG. 7D. The adhesive material of the adhesive layer can be conductive. The adhesive of the adhesive layer can be a pressure sensitive adhesive, a hot melt adhesive, or a heat, moisture or radiation curable adhesive. The lamination adhesive can be post cured by radiation, e.g., UV, through the top conductive layer if the top conductive layer is radiation transparent. In other embodiments, multiple electrodes can be bonded directly to the sealed array of microcells.

[0072] In general, the microcells may be of any shape, and their size and shape may vary. The microcells may be of substantially uniform size and shape in a system. However, it is possible to have microcells of a mixture of shapes and sizes. The openings of the microcells may be circular, square, rectangular, hexagonal, or any other shape. The size of the partition area between the openings may also vary. The dimensions of each individual microcell are approximately 1×10 1 ~Approx. 1×10 6 μm 2 , or approximately 1 × 10 2 ~Approx. 1×10 6 μm 2 , or approximately 1 × 10 3 ~Approx. 1×10 5 μm 2 The range may be:

[0073] The depth of the microcells may range from about 5 μm to about 200 μm, or from about 10 μm to about 100 μm. The ratio of the opening area to the total area ranges from 0.05 to 0.95, preferably from 0.4 to 0.9.

[0074] An electrophoretic display usually includes a layer of electrophoretic material and at least two other layers disposed on either side of the electrophoretic material, one of these two layers being an electrode layer. In most such displays, both layers are electrode layers, and one or both of the electrode layers are patterned to define the pixels of the display. For example, one electrode layer may be patterned into elongated row electrodes and the other into elongated column electrodes extending at right angles to the row electrodes, the pixels being defined by the intersections of the row and column electrodes. Alternatively, and more commonly, one electrode layer has the form of a single continuous electrode, and the other electrode layer is patterned into a matrix of pixel electrodes, each of which defines one pixel of the display. In another type of electrophoretic display, intended for use with a stylus, printhead or similar movable electrode that is separate from the display, only one of the layers adjacent to the electro-optic material layer contains electrodes; the layer on the opposite side of the electro-optic material layer is typically a protective layer intended to prevent the movable electrode from damaging the electro-optic material layer.

[0075] The manufacture of a three-layer electrophoretic display usually involves at least one lamination operation. For example, some of the aforementioned MIT and E Ink patents and applications describe methods for producing encapsulated electrophoretic displays in which an encapsulated electrophoretic medium, including capsules in a binder, is coated onto a flexible substrate including indium tin oxide (ITO) or a similar conductive coating coated onto a plastic film. Separately, a backplane is prepared that includes an array of pixel electrodes and conductors in a suitable arrangement to connect the pixel electrodes and drive the circuitry. To form the final display, the substrate having the electro-optical material layer is laminated to the backplane using a lamination adhesive.

[0076] The aforementioned U.S. Patent No. 6,982,178 describes a method of assembling a solid electro-optic display that is well suited for mass production. Essentially, this patent describes a so-called "front plane laminate" ("FPL"), which includes, in order, a light-transmissive electrode layer, an electro-optic material layer in electrical contact with the light-transmissive electrode layer, an adhesive layer, and a release sheet, as shown in FIG. 3. Typically, the light-transmissive electrode layer is carried on a light-transmissive substrate, which is preferably flexible in the sense that it can be wrapped by hand around a 10 inch (254 mm) diameter drum (for example) without undergoing permanent deformation. The term "light-transmissive" is used in this patent and herein to mean that the layer so designated transmits sufficient light to enable an observer looking through the layer to observe a change in the display state of the electrophoretic medium, which change is normally seen through the light-transmissive electrode layer and the adjacent substrate (if present). When the electrophoretic medium exhibits a change in reflectivity of non-visible wavelengths, the term "light transmissive" should of course be interpreted as referring to the transmission of the relevant non-visible wavelengths. The substrate is typically a polymer film, usually having a thickness in the range of about 1 to about 25 mils (25 to 634 μm), preferably about 2 to about 10 mils (51 to 254 μm). The light transmissive electrode layer can conveniently be a thin metal or metal oxide layer, for example, aluminum or ITO, or a conductive polymer. Poly(ethylene terephthalate) (PET) films coated with aluminum or ITO are commercially available, for example, as "aluminized Mylar" ("Mylar" is a registered trademark) from EI du Pont de Nemours & Company, Wilmington, DE, and such commercially available materials can be used with good results in the front plane laminate.Assembly of an electrophoretic display using such a front plane laminate may be performed by removing the release sheet from the front plane laminate and contacting the adhesive layer with the backplane under conditions effective to adhere the adhesive layer to the backplane, thereby securing the adhesive layer, the electro-optic material layer, and the light-transmissive electrode layer to the backplane. This process is well suited to mass production, as the front plane laminate can be mass-produced, typically using roll-to-roll coating techniques, and then cut into pieces of any size required for use with a particular backplane.

[0077] No. 7,561,324 describes a so-called "dual release sheet," which is essentially a simplification of the front plane laminate of the aforementioned U.S. Pat. No. 6,982,178. One form of dual release sheet includes a layer of electro-optic material sandwiched between two adhesive layers, one or both of which are covered by a release sheet, as shown in FIG. 4. Another form of dual release sheet includes a layer of solid electro-optic material sandwiched between two release sheets. Both forms of dual release film are intended for use in a process generally similar to the process for assembling electrophoretic displays from front plane laminates already described, but involving two separate laminates. Typically, in a first laminate, the dual release sheet is laminated to a front electrode to form a front subassembly, and then in a second laminate, the front subassembly is laminated to a backplane to form the final display, although these two stacking orders can be reversed if desired.

[0078] No. 7,839,564 describes a so-called "inverted front plane laminate," which is a variation of the front plane laminate described in the aforementioned U.S. Pat. No. 6,982,178. The inverted front plane laminate may include, in order, at least one of a light-transmissive protective layer and a light-transmissive electrode layer, an adhesive layer, an electro-optic material layer, and a release sheet. The inverted front plane laminate is used to form an electro-optic device having a layer of laminating adhesive between the electro-optic material layer and the light-transmissive electrode layer, with or without a typically thin second adhesive layer between the electro-optic material layer and the backplane. Such electro-optic displays can combine good resolution with good low temperature performance.

[0079] Electrophoretic medium.

[0080] Electrophoretic medium, in the context of the present invention, refers to a composition in a microcell. The microcell may be filled with at least one type of charged pigment particles in a non-polar fluid for display applications. The electrophoretic medium may contain one type of charged type particles, or one or more types of particles having different colors, charges and charge polarities. The charged particles move in the electrophoretic medium under the influence of an electric field applied across the electro-optical material layer. The charged particles may be inorganic or organic pigments having a polymer surface treatment to improve their stability. The electrophoretic medium may contain pigments having white, black, cyan, magenta, yellow, blue, green, red, and other colors. The electrophoretic medium may also contain charge control agents, charge adjuvants, rheology modifiers, and other additives. Examples of non-polar fluids include hydrocarbons such as Isopar, decahydronaphthalene (decalin), 5-ethylidene-2-norbornene, fatty oils, paraffin oils, silicon fluids, aromatic hydrocarbons such as toluene, xylene, phenylxylylethane, dodecylbenzene or alkylnaphthalenes, halogenated solvents such as perfluorodecalin, perfluorotoluene, perfluoroxylene, dichlorobenzotrifluoride, 3,4,5-trichlorobenzotrifluoride, chloropentafluoro-benzene, dichlorononane or pentachlorobenzene, and perfluorinated solvents such as FC-43, FC-70 or FC-5060 from 3M Company, St. Paul MN, low molecular weight halogen-containing polymers such as poly(perfluoropropylene oxide) from TCI America, Portland, Oregon, poly(chlorotrifluoro-ethylene) from Halocarbon Product Corp., River Examples of suitable oils include halocarbon oils manufactured by Edge, NJ; perfluoropolyalkyl ethers such as Galden manufactured by Ausimont; or Krytox oils and Greases K-Fluid series manufactured by DuPont, Delaware; and polydimethylsiloxane-based silicone oil (DC-200) manufactured by Dow-corning.

[0081] The electrophoretic medium may contain two types of charged particles having different colors, a first type of charged particles having a first charge polarity and a second type of charged particles having a second charge polarity opposite to the first charge polarity. The first type of charged particles may be black and the second type of charged particles may be white.

[0082] The electrophoretic medium may contain three types of charged particles all having different colors, a first type of charged particles having a first charge polarity, a second type of charged particles having a second charge polarity opposite to the first charge polarity, and a third type of charged particles having a third charge polarity the same as the first or second charge polarity. The first type of charged particles may be black, the second type of charged particles may be white, and the third type of charged particles may be selected from the group consisting of red, yellow, blue, cyan, magenta, green, and orange.

[0083] The electrophoretic medium may contain four types of charged particles, all having different colors, with a first type of charged particles having a first charge polarity, a second type of charged particles having a first charge polarity, a third type of charged particles having a second charge polarity opposite to the first charge polarity, and a fourth type of charged particles having a second charge polarity. The magnitude of the charge of the first type of particles may be higher than the magnitude of the charge of the second type of particles, and the magnitude of the charge of the third type of particles may be higher than the charge of the fourth type of particles. In one example, the first type of charged particles is cyan, the second type of charged particles is magenta, the third type of particles is yellow, and the fourth type of charged particles is white.

[0084] The electrophoretic medium may contain four types of charged particles, all having different colors, with a first type of charged particles having a first charge polarity, a second type of charged particles having a first charge polarity, a third type of charged particles having a first charge polarity, and a fourth type of charged particles having a second charge polarity opposite to the first charge polarity. The magnitudes of charge of the first, second, and third particles may be different from each other. The magnitude of charge of the third type of particles may be higher than the magnitude of charge of the first type of particles, and the magnitude of charge of the first type of particles may be higher than the magnitude of charge of the second type of particles. In one example, the first type of particles is cyan, the second type of particles is magenta, the third type of particles is yellow, and the fourth type of particles is white.

[0085] The electrophoretic medium may contain five types of charged particles, all having different colors, where a first type of charged particles has a first charge polarity, a second type of charged particles has a first charge polarity, a third type of particles has a first charge polarity, a fourth type of particles has a second charge polarity opposite to the first charge polarity, and a fifth type of particles has a second charge polarity. The magnitudes of the first, second, and third charges may be different from each other. The magnitude of the charge of the third type of particles may be higher than the magnitude of the charge of the first type of particles, and the magnitude of the charge of the first type of particles may be higher than the magnitude of the charge of the second type of particles. The charge of the fourth type of particles may have a higher charge than the fifth type of charged particles. In one example, the first type of particles are cyan, the second type of particles are magenta, the third type of particles are black, the fourth type of particles are yellow, and the fifth type of particles are white.

[0086] Sealing film from aqueous sealing composition

[0087] The sealing film that seals the openings of the microcells of an electro-optic display must provide a barrier to the electrophoretic medium so that non-polar fluids are not removed from the microcells, and further, the sealing film must not negatively affect the electro-optic performance of the device.

[0088] One of the important properties of the sealing film is its electrical volume resistivity. If the volume resistivity of the sealing film is too high, a significant voltage drop occurs within the sealing film, necessitating a voltage increase across the electrodes to operate the device. Increasing the voltage across the electrodes in this manner is undesirable, as it increases the power consumption of the display and may require the use of more complex and expensive control circuitry to handle the increased voltage. On the other hand, if the volume resistivity of the sealing film is too low, undesirable crosstalk between adjacent pixel electrodes may be observed, resulting in poor image quality (blooming). In addition, since volume resistivity typically increases rapidly with decreasing temperature, too high a volume resistivity of the sealing film will have a negative effect on the electro-optical performance of the display at low temperatures. The sealing film should be 10 8 The seal film can have a volume resistivity of 3.5×10 ohm.cm or higher. 7 ~10 12 ohm.cm or 10 8 ~10 10 The sealing film may have a volume resistivity of 10 ohm.cm. 10 It may have a volume resistivity of ohm.cm or less.

[0089] Another important property of the sealing film besides the barrier properties and volume resistivity is its moisture absorption: if the sealing film absorbs significant amounts of moisture from the environment over time, the electro-optical performance of the device may become poor.

[0090] The sealing film can be prepared from an aqueous sealing composition comprising a water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer in a content of 14% to 55% by weight based on the weight of the aqueous sealing composition excluding water, a polyurethane in a content of 6% to 27% by weight based on the weight of the aqueous sealing composition excluding water, carbon black in a content of 5% to 64% by weight based on the weight of the aqueous sealing composition excluding water, a water-soluble ether in a content of 1.0% to 40% by weight based on the weight of the aqueous sealing composition excluding water, and water in a content of 20% to 95% by weight based on the weight of the aqueous sealing composition.

[0091] Poly(vinyl alcohol) homopolymers have a degree of hydrolysis of 90% to 99.5%. Poly(vinyl alcohol-co-ethylene) copolymers have a degree of hydrolysis of 90% to 99.5% and an ethylene content of less than 10%. The degree of hydrolysis of poly(vinyl alcohol) homopolymers and poly(vinyl alcohol-co-ethylene) copolymers can be 92% to 99%, or 92% to 95%. The ethylene content of poly(vinyl alcohol-co-ethylene) copolymers can be less than 9%, or less than 8.5%, or less than 8%. The degree of hydrolysis of polyvinyl alcohol homopolymers and copolymers is conventionally reported by the manufacturers of such polymers and indicates the ratio in moles of vinyl alcohol units in the polymer to the total vinyl units. The other units are typically vinyl acetate (ester). The ethylene content of poly(vinyl alcohol-co-ethylene) copolymers is also reported by the manufacturers and indicates the ratio in moles of ethylene units in the polymer to the other units. In this case, the other units are vinyl alcohol and vinyl acetate. The poly(vinyl alcohol) homopolymers and poly(vinyl alcohol-co-ethylene) copolymers of the aqueous sealing composition can have a weight average molecular weight of 1,000 to 1,000,000 daltons, or 10,000 to 500,000 daltons, or 20,000 to 400,000 daltons.

[0092] The content of the water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer in the aqueous sealing composition can be 14% to 53% by weight, or 25% to 50% by weight, or 30% to 48% by weight, or 33% to 46% by weight, based on the weight of the aqueous sealing composition excluding water.

[0093] Polyurethanes are typically prepared by a polyaddition process involving diisocyanates. Non-limiting examples of polyurethanes include polyether polyurethanes, polyester polyurethanes, polycarbonate polyurethanes, polyether polyureas, polyureas, polyester polyureas, polyester polyureas, polyisocyanates (e.g., polyurethanes containing isocyanate linkages), and polycarbodiimides (e.g., polyurethanes containing carbodiimide linkages). Generally, polyurethanes contain urethane groups. The polyurethanes utilized in the aqueous sealing compositions and sealing films described herein can be prepared using methods known in the art. The polyurethanes of the aqueous sealing compositions of the present invention are polyester polyurethanes, polycarbonate polyurethanes, and mixtures thereof. The polyurethanes of the aqueous sealing compositions can have a weight average molecular weight of 1,000 to 2,000,000 daltons, or 10,000 to 300,000 daltons, or 15,000 to 200,000 daltons. The polyurethane may be added to the water-based sealing composition as an aqueous solution, dispersion or emulsion, or as a latex.

[0094] The content of polyurethane in the aqueous sealing composition may be 7% to 27% by weight, or 9% to 24% by weight, or 11% to 22% by weight, or 12% to 20% by weight, based on the weight of the aqueous sealing composition excluding water.

[0095] The aqueous sealing composition may include a crosslinking agent (also called a crosslinking agent) in an amount of 0.1% to 8% by weight of the crosslinking agent based on the weight of the aqueous sealing composition excluding water. The crosslinking agent forms chemical bonds between the polyurethane of the aqueous sealing composition and potentially the polymer molecules of the microcell during the curing of the aqueous sealing composition to prepare the sealing film, thereby increasing the adhesion between the sealing film and the microcell. The crosslinking agent is preferably soluble or dispersible in the aqueous carrier of the aqueous sealing composition. The crosslinking agent may be a monomer, oligomer or polymer. Examples of crosslinking agents include polyisocyanates, polyfunctional polycarbodiimides, polyfunctional aziridines, silane coupling agents, boron / titanium / zirconium-based crosslinkers, or melamine formaldehyde. The polycarbodiimide crosslinking agent is reactive at acidic pH conditions. Preferably, the crosslinking agent does not include a sulfosuccinate surfactant. The content of the crosslinking agent in the aqueous sealing composition may be 0.1% to 5% by weight, or 0.2% to 4% by weight, or 0.3% to 3.5% by weight, or 0.5% to 3% by weight, or 0.8% to 2.6% by weight, based on the weight of the aqueous sealing composition excluding water.

[0096] The present inventors have found that an aqueous sealing composition comprising a combination of a water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer and a polyurethane, where the interfacial tension between the water-soluble poly(vinyl alcohol) polymer or poly(vinyl alcohol-co-ethylene) copolymer and the polyurethane is less than 2 mN / m, can form a sealing film with excellent performance.

[0097] Extensive experimental studies have also revealed that superior performance has been observed from water-based sealing compositions containing a combination of water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer and polyurethane, where the polar component of the polyurethane surface energy is between 10 and 20 mN / m.

[0098] The aqueous sealing composition may also include a conductive filler in a content of 5% to 64% by weight based on the weight of the aqueous sealing composition excluding water. The filler of the aqueous sealing composition may be selected from the group consisting of carbon black, graphene, graphite, and carbon nanotubes. The filler reduces the volume resistivity of the sealing film, but may also affect other properties of the layer, such as its surface energy. To be useful as a filler, carbon black must have good dispersibility in the aqueous sealing composition. The content of the conductive carbon black in the aqueous sealing composition may be 10% to 55% by weight, or 20% to 50% by weight, or 25% to 45% by weight, or 30% to 40% by weight of the aqueous sealing composition.

[0099] The oil absorption of the carbon black used in the aqueous sealing composition is 100 cm per 100 mg of carbon black. 3 Oil absorption is typically reported by carbon black manufacturers as OAN, measured using a method according to ASTM 2414. It represents the degree of structure and agglomeration of the carbon black particles. That is, the higher the OAN, the more structured (connected to each other and having a branched structure) the carbon black particles are and / or the particles are more aggregated. More structured / aggregated carbon blacks can generally provide higher electrical conductivity to the sealing film, but the electrical conductivity can also vary depending on the dispersibility of the filler, with higher OAN indicating that the carbon black can be difficult to disperse. The carbon black filler of the aqueous sealing composition can preferably have an average diameter of the primary particles greater than 30 nm. The average diameter is another physical property of the carbon black grade that can be reported by the carbon black manufacturer. The primary particles can be determined by electron microscopy. Typically, carbon blacks with very small average diameter primary particles are difficult to disperse. Carbon blacks have a mean diameter of 80 nm or more. 2 / g or less than 75m 2 / g or less than 70m 2The carbon black may have a total surface area of ​​less than 0.1 ohm.cm / g. Total surface area is another common physical property routinely reported by carbon black manufacturers. Total surface area is measured using a nitrogen adsorption method according to ASTM D 6556. The carbon black may have a volume resistivity of greater than 0.1 ohm.cm, measured in powder form at a pressure of 40 MPa using ASTM D 2663 method.

[0100] The total surface energy of the conductive carbon black of the water-based sealing composition may be higher than 40 mN / m, or higher than 55 mN / m, as determined using the Washburn method with hexane as the test liquid. The total surface energy of the conductive carbon black of the water-based sealing composition may be 40 mN / m to 80 mN / m, or 40 mN / m to 70 mN / m, or 40 mN / m to 65 mN / m. The dispersive component of the surface energy of the conductive carbon black may be higher than 15 mN / m, as determined using the Washburn method with hexane as the test liquid. The dispersive component of the conductive filler may be 15 mN / m to 40 mN / m, or 15 mN / m to 30 mN / m.

[0101] The aqueous sealing composition contains 1.0% to 40% by weight of the water-soluble ether, based on the weight of the aqueous sealing composition excluding water. The aqueous sealing composition may contain 1.5% to 35% by weight, or 2.0% to 30% by weight, or 2.5% to 25% by weight, or 4.0% to 22% by weight, or 5.0% to 20% by weight of the water-soluble ether, based on the weight of the aqueous sealing composition excluding water. The content of the water-soluble ether in the aqueous sealing composition may be greater than 1.7% by weight, or greater than 2% by weight, or greater than 3% by weight, or greater than 4% by weight, or greater than 5% by weight, or greater than 6% by weight, or greater than 7% by weight, or greater than 8% by weight, or greater than 10% by weight, or greater than 12% by weight, or greater than 15% by weight. The content of the water-soluble ether in the aqueous sealing composition may be lower than 40% by weight, or lower than 30% by weight, or lower than 25% by weight, based on the weight of the aqueous sealing composition excluding water.

[0102] The water-soluble ether has a weight average molecular weight of 75 to 5,000 daltons. The water-soluble ether can have a weight average molecular weight of 85 to 3,000 daltons, or 90 to 1,000 daltons, or 90 to 500 daltons, or 90 to 300 daltons. The water-soluble ether can have a weight average molecular weight of greater than 75, or greater than 90, or greater than 100, or greater than 200. The water-soluble ether can have a weight average molecular weight of less than 5,000, or less than 3,000, or less than 1,000, or less than 500, or less than 300, or less than 200, or less than 150.

[0103] Water-soluble ethers are polar compounds that are soluble in water and polar organic solvents. Water-soluble ethers can be represented by Formula I, Formula II, or Formula III. [ka] [ka] The value of n is 1 to 145. The value of n can be 1 to 100, or 1 to 50, or 1 to 20, or 1 to 10, or 1 to 5, or 1 to 4, or 1 to 3, or 1 to 2. R1 is hydrogen, a methyl or ethyl group, and R2, R3, R4, R5, R6, and R7 are independently selected from the group consisting of hydrogen, a straight or branched alkyl group containing 1 carbon atom to 6 carbon atoms, phenyl, and a benzyl group. Formula I includes at least one ether functional group. Formula II includes at least one ether functional group. Formula III includes at least one ether functional group.

[0104] The water-soluble ethers are ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-n-propyl ether, ethylene glycol monoisopropyl ether, ethylene glycol n-monobutyl ether, ethylene glycol monoisobutyl ether, ethylene glycol mono-t-butyl ether, ethylene glycol monobenzyl ether, ethylene glycol monophenyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol di-n-propyl ether, ethylene glycol diisopropyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol mono-n-propyl ether, diethylene glycol monoisopropyl ether, diethylene glycol n-monobutyl ether, diethylene glycol monoisobutyl ether, diethylene glycol mono-t-butyl ether, diethylene glycol monobenzyl ether, diethylene glycol monophenyl ether, diethylene glycol dimethyl ether, diethylene glycol Licor diethyl ether, diethylene glycol ethyl methyl ether, diethylene glycol di-n-propyl ether, diethylene glycol diisopropyl ether, diethylene glycol di-n-butyl, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol mono-n-propyl ether, triethylene glycol monoisopropyl ether, triethylene glycol n-monobutyl ether, triethylene glycol monoisobutyl ether, triethylene glycol mono-t-butyl ether, triethylene glycol monobenzyl ether, triethylene glycol monophenyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol di-n-propyl ether, triethylene glycol diisopropyl ether, tetraethylene glycol monomethyl ether, tetraethylene glycol monoethyl ether, triethylene glycol monophenyl ether, tetraethylene glycol dimethyl ether, polyethylene glycol monomethyl ether,Polyethylene glycol monoethyl ether, polyethylene glycol monophenyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono-n-propyl ether, propylene glycol monoisopropyl ether, propylene glycol mono-n-butyl ether, propylene glycol monoisobutyl ether, propylene glycol monophenyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol mono-n-propyl ether, dipropylene glycol mono The propylene glycol monoisopropyl ether, dipropylene glycol mono-n-butyl ether, dipropylene glycol monoisobutyl ether, dipropylene glycol dimethyl ether, dipropylene glycol diethyl ether, dipropylene glycol di-n-propyl ether, dipropylene glycol diisopropyl ether, tripropylene glycol monomethyl ether, tripropylene glycol monoethyl ether, tripropylene glycol mono-n-propyl ether, tripropylene glycol monoisopropyl ether, tripropylene glycol mono-n-butyl ether, tripropylene glycol monoisobutyl ether, or mixtures thereof.

[0105] The aqueous sealing composition may also include a rheology modifier in a content of 0.05% to 10% by weight, or 0.05% to 5% by weight, or 0.1% to 3% by weight, based on the weight of the aqueous sealing composition excluding water. The rheology modifier increases the stability of the aqueous sealing composition during storage. The rheology modifier also promotes film formation, improves seal stability, and provides other functions. Examples include associative thickeners, alkali-swellable acrylic emulsions, and other polymeric thickeners. The aqueous sealing composition may be shear thinning, i.e., its viscosity is reduced at higher shear. For example, the rheology profile of the aqueous sealing composition may be 10 -4 Viscosity at a shear rate of 1 / sec and 10 2The seal film may exhibit a viscosity reduction of 5 to 10,000 times between the viscosity at a shear rate of 1 / sec. The seal film may also include a rheology modifier in an amount of 0.05% to 10% by weight, or 0.05% to 5% by weight, or 0.1% to 3% by weight, based on the weight of the seal film.

[0106] The aqueous sealing composition may also include a wetting agent, also called a surfactant. Non-limiting examples of wetting agents include FC surfactants from 3M Company, Zonyl fluorosurfactants, fluoroacrylates, fluoromethacrylates, fluoro-substituted long-chain alcohols, perfluoro-substituted long-chain carboxylic acids and their derivatives from DuPont, and Silwet silicone surfactants from OSi, Greenwich, Conn. The wetting agent may increase the affinity between the sealing film and the microcell, enhance the interfacial area therebetween, improve the adhesion of the sealing film to the microcell, and provide a more flexible coating process. The content of the wetting agent in the aqueous sealing composition may be 0.01% to 3.0% by weight, or 0.04% to 2.0% by weight, or 0.06% to 1.0% by weight, or 0.07% to 0.8% by weight, based on the weight of the aqueous sealing composition excluding water. The sealing film may include a wetting agent. The content of the wetting agent in the seal film may be 0.01% to 3.0% by weight, or 0.04% to 2.0% by weight, or 0.06% to 1.0% by weight, or 0.07% to 0.8% by weight, based on the weight of the seal film.

[0107] The aqueous sealing composition may comprise 20% to 95% by weight, or 50% to 94% by weight, or 70% to 92% by weight, or 75% to 90% by weight, or 80% to 88% by weight of water, based on the weight of the aqueous sealing composition.

[0108] The aqueous sealing composition may also include a pH adjuster. The pH adjuster is added to the aqueous sealing composition to adjust its pH to a value of 6.5 to 8.5. One example of a pH adjuster is ammonium hydroxide, but various acids and bases can be used. The pH adjuster can increase the pH of the aqueous sealing composition, thereby reducing the crosslinking rate of the aqueous sealing composition before use, and also provide optimal pH conditions for the rheology modifier to interact with the particles of the aqueous sealing composition, improving its effectiveness. The pH adjuster can be used in an amount of 0.2% to 1% by weight based on the weight of the aqueous sealing composition excluding water.

[0109] The aqueous sealing composition can be used to form a sealing film by applying the aqueous sealing composition and drying or curing the aqueous sealing composition. The sealing film can include most of the components of the aqueous sealing composition. If the aqueous composition includes a crosslinking agent, the crosslinking agent is incorporated into the polyurethane polymer of the sealing film during curing. In addition, the water of the sealing composition evaporates during drying or curing of the aqueous sealing composition to prepare the sealing film. Experimental data shows that approximately 37% by weight of the initially added water-soluble ether also evaporates during drying or curing, and only approximately 63% by weight of the initially added water-soluble ether content of the aqueous sealing composition is present in the sealing film. If any water or moisture remaining or absorbed in the sealing film is present, the content of the components of the disclosed sealing film is calculated as the weight % of the component relative to the weight of the aqueous sealing composition excluding the remaining or absorbed water, unless otherwise stated.

[0110] The seal film comprises a water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer in a content of 15% to 60% by weight based on the weight of the seal film, the poly(vinyl alcohol) homopolymer having a degree of hydrolysis of 90% to 99.5% and the poly(vinyl alcohol-co-ethylene) copolymer having a degree of hydrolysis of 90% to 99.5% and an ethylene content of less than 10%. The seal film also comprises a polyurethane in a content of 7% to 29% by weight based on the weight of the seal film, a carbon black in a content of 5% to 70% by weight based on the weight of the seal film, and a water-soluble ether in a content of 0.5% to 25% by weight based on the weight of the seal film. The water-soluble ether can have a molecular weight of 90 to 5,000 daltons. The water-soluble ether can optionally contain a hydroxyl group.

[0111] The physical and chemical properties of the various classes of seal film components have been detailed above.

[0112] The content of the water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer in the sealing film may be 16% to 55% by weight, or 28% to 52% by weight, or 33% to 50% by weight, or 35% to 48% by weight, based on the weight of the sealing film.

[0113] The content of polyurethane in the seal film may be 8% by weight to 29% by weight, or 10% by weight to 26% by weight, or 12% by weight to 24% by weight, or 14% by weight to 22% by weight, based on the weight of the seal film.

[0114] The sealing film may contain conductive carbon black in an amount of 11% to 60% by weight, or 24% to 55% by weight, or 29% to 50% by weight, or 30% to 45% by weight, based on the weight of the sealing film.

[0115] The seal film contains a water-soluble ether in a content of 0.5 wt% to 25 wt% based on the weight of the seal film. The seal film may contain a water-soluble ether in a content of 0.8 wt% to 20 wt%, or 1.0 wt% to 18 wt%, or 1.2 wt% to 20 wt%, or 1.5 wt% to 18 wt%, or 2.0 wt% to 16 wt% based on the weight of the seal film. The content of the water-soluble ether in the seal film may be higher than 0.5 wt%, or higher than 0.6 wt%, or higher than 0.7 wt%, or higher than 0.8 wt%, or higher than 0.9 wt%, or higher than 1 wt%, or higher than 1.5 wt%, or higher than 2.0 wt%, or higher than 3.0 wt%, or higher than 4 wt% based on the weight of the seal film. The content of the water-soluble ether in the seal film may be less than 25% by weight, or less than 20% by weight, or less than 18% by weight, or less than 15% by weight, or less than 12% by weight, or less than 10% by weight, based on the weight of the seal film.

[0116] The sealing film prepared by the aqueous sealing composition can be used to seal microcells of an electro-optical device, which includes a conductive layer, a microcell layer including a plurality of microcells, each microcell including an opening, each microcell including an electrophoretic medium, the electrophoretic medium including charged particles in a non-polar carrier, a sealing film, the sealing film spanning the opening of each microcell, an adhesive layer, and an electrode layer.

[0117] In general, the sealing film of an electro-optical device plays an important role in the display performance. Poor barrier properties of the sealing film lead to the outflow of non-polar fluid of the electrophoretic medium from the electro-optical material layer over time, thereby causing serious degradation of the electro-optical performance of the display. It has been observed that increasing the content of poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer in the sealing film improves its barrier properties. However, sealing films having a high content of poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer increase the moisture absorption of the layer, which is also undesirable.

[0118] The inventors have surprisingly found that optimal electro-optical performance in terms of color gamut can be achieved when the seal film comprises a combination of poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer and polyurethane, conductive carbon black, and a water-soluble ether having a molecular weight of 75 to 5,000 Daltons. The addition of the water-soluble ether to the aqueous seal composition and seal film is believed to reduce the electrical resistance of one or both interfaces of the seal film and adjacent layers, such as the seal film adhesive interface and the seal film electrophoretic medium interface. This reduction in electrical resistance at the interface has been experimentally demonstrated using volume resistivity measurements and using electrical impedance spectroscopy experiments, as shown in the Examples section. Importantly, this electrical resistance at the interface did not affect the electrical conductivity of the seal film itself. In fact, as the data shows, the seal film of the present invention has a higher volume resistivity than that of a control film that does not contain a water-soluble ether. As previously mentioned, the higher volume resistivity of the seal film contributes to reduced blooming, a phenomenon well known in the electro-optical field.

[0119] Improved performance is also observed when a combination of poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer and polyurethane is used, and the interfacial tension between the poly(vinyl alcohol) polymer or poly(vinyl alcohol-co-ethylene) copolymer and the polyurethane is less than 2 mN / m. Moreover, the inventors have surprisingly found that optimal performance is also observed when a combination of poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer and polyurethane is used, and the polar component of the surface energy of the polyurethane is between 10 and 20 mN / m.

[0120] These and other aspects of the present invention will be further understood in light of the following examples, which are intended to illustrate certain embodiments of the invention but are not intended to limit its scope, as defined by the claims. EXAMPLES

[0121] How to evaluate seal films

[0122] A. Examples of Preparation of Aqueous Seal Compositions

[0123] A1. Example of Preparation of Carbon Black Dispersion. An aqueous solution of poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer was prepared containing 20% ​​by weight of polymer relative to the volume of the solution. In one example, the polymer is poly(vinyl alcohol-co-ethylene) copolymer (Exceval® RS-1717 supplied by Kuraray). That is, the solution contains 200 g of polymer per liter of solution. Carbon black powder is mixed with the aqueous solution of poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer. In one example, an aqueous solution containing 106 g of poly(vinyl alcohol-co-ethylene) copolymer was mixed with 162 g of carbon black (Nerox® 3500 supplied by Orion Engineered Carbon). The dispersion was mixed in an overhead mixer (Hei-Torque Value 200) at 300 rpm for 30 minutes. The dispersion is then recirculated through a Generation 1 Q1375 Flocell sonicator and the sonicator jacket is cooled using cold water at 10° C. for 3 hours 23 minutes at 100% amplitude. The dispersion was continuously stirred until it was used to prepare the seal composition.

[0124] A2. Examples of preparation of aqueous sealing compositions. In a container, an aqueous polyurethane dispersion was combined with a wetting agent and an aqueous solution of a poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer. In one example, 194 g of a 35 wt % polyurethane aqueous dispersion (L3838 aqueous dispersion supplied by Hauthaway) was mixed with 372 g of an aqueous solution of a poly(vinyl alcohol-co-ethylene) copolymer (containing 20 wt % copolymer by volume of the solution). In this example, the poly(vinyl alcohol-co-ethylene) copolymer was Exceval™ RS-1717 supplied by Kuraray. The mixture was mixed for 10 minutes at 90 rpm using a Hei-torque Value 200 overhead mixer. The appropriate amount of dipropylene glycol dimethyl ether (45 g in one example) was then added over a period of 5 minutes while continuing to mix at 90 rpm. The resulting mixture was mixed for an additional 10 minutes at 90 rpm and the appropriate amount of crosslinker was added. The mixture was mixed at 90 rpm for an additional 60 minutes. The appropriate amount of carbon black dispersion prepared in A1 was added (1.39 L in one example) and the resulting dispersion was mixed at 500 rpm for 60 minutes. The pH was then adjusted to 6.5-8.5 using ammonium hydroxide and the dispersion was mixed for an additional 30 minutes. The appropriate amount of rheology modifier was added dropwise to the dispersion and mixing was continued for an additional 60 minutes. The dispersion was then degassed under reduced pressure (25 mmHg) for 5 days. The resulting aqueous sealing composition was used for the preparation of a sealing film for the corresponding device within 7 days of preparing the sealing composition.

[0125] B1. Example of preparation of sealing film using the drawdown method.

[0126] The sealing composition prepared in A2 above was coated onto the indium tin oxide (ITO) side of the ITO-PET film using a Gardco drawdown coater. A square applicator with a 15 mil gap and 8 passes was used. The drawdown speed was set at 2 m / min to target a dry film thickness of 30 + / - 2 μm. The coating was dried in an oven at 100°C for 15 minutes. The dried film was conditioned at 25°C and 55% RH for 24 hours.

[0127] B2. Example of preparation of sealing film using roll-to-roll coating line.

[0128] The sealing composition prepared in A2 above was coated onto the indium tin oxide (ITO) side of a 30 μm dry thickness ITO-PET thin film using a slot die on a roll-to-roll coating line at a speed of 9 ft / min. The film was passed through a convection oven consisting of four heating zones at a speed of 9 ft / min. Each heating zone was 5 feet in length. The first zone was set at a temperature of 80° C. and the remaining heating zones were set at a temperature of 100° C. Once dried, the sealing film on the ITO-PET was passed through a drying oven and the film was cut into three pieces, each approximately 24-30 inches long, and placed in a clean room with a controlled environment at a temperature of 25° C. and 55% relative humidity (RH).

[0129] C. Determination of volume resistivity – TCBC method.

[0130] The seal film prepared by the above-mentioned method B2 (method of preparation of seal film) was evaluated for volume resistivity. The "TCBC method" was used to describe the transient background current method of measuring volumetric resistivity. For the determination of volume resistivity, Labview 2014 software and TCBC waveform program, NI USB 6211 multifunction device, and model 603 power amplifier were used. The device allows the user to measure the volumetric resistivity of the electrode laminated sample by applying a waveform at a preset voltage, measuring the output current and calculating the resistance. The method included (a) preparation of the seal film according to the previously disclosed "method of preparation of seal film" B2, (b) lamination method with conductive adhesive and graphite backplane of the seal film, and (c) test method using the waveform program and setup. The thickness of the film was measured using a Mitutoyo model S112EXB thickness gauge. After the lamination process, the sample was conditioned at 25°C / 55% RH for 10 days before testing. The reported resistance and measured thickness were then used to calculate the volume resistivity using the following equation: r=R / t, where r is the resistivity, R is the resistivity, and t is the thickness.

[0131] One panel of each seal coated on ITO-PET was collected from the roll-to-roll coating line described in Method B2 above. The seal was cut into 12 inch long pieces. The 12 inch long pieces were cut to 4.5 inch width as shown in the image in Figure 8A. The excess ITO on the edges was not trimmed off.

[0132] Graphite backplane preparation: One sheet (5 pixels) of graphite backplane per seal film was collected for testing. One of the pixels was cut off from the end so that only 4 pixels remained. The top edge and the side edge (where the pixel line runs) were cut off as shown in the image of Figure 8B. The other side edge was not cut off.

[0133] Preparation of KA2 Film: A long roll of qualified 6 μm thick KA2 conductive adhesive film was collected for use in testing. The KA2 film was cut into 3 inch wide pieces. The 3 inch wide pieces were cut to 10 inch lengths as shown in the image in FIG. 8C. Only one side was cut so that an overhang of the release liner remained on the other side.

[0134] Lamination of TCBC samples: Conductive adhesive KA2 with a thickness of 6 μm was laminated onto the dried seal film via a hot roll laminator. For this lamination, the bottom plate and top roller of the laminator were set at 80° C., and the speed of lamination was set at 17 mm / sec. The cut KA2 film was taped to the cut seal, with the protective sheet on the KA2 touching the seal. The bottom and right edges of the KA2 film were aligned with the bottom and right edges of the seal. The top of the KA2 film was taped to the seal. The top of the seal was taped to the laminator plate so that the top edge of the seal was directly under the center of the roller. While holding the top sheet with the KA2, the KA2 protective sheet was gently removed. Still holding the KA2, lamination began by slowly pressing the KA2 onto the seal with the roller. After lamination was done, the tape was removed and the layer was released from the KA2. The graphite backplane was carefully placed on the KA2. The electrode was placed in the center of the KA2. The sample was laminated and the final preparation is shown in Figure 8D. The final TCBC sample 800 included an ITO / PET conductive film 801, a seal film 802, a KA2 adhesive 803, and a graphite backplane 804. An area of ​​the conductive film 801 and a first test point on the graphite backplane 804 were electrically connected via a voltage source. The sample was then conditioned at 25°C / 55% RH for 10 days to ensure complete humidification.

[0135] Testing of TCBC samples: After conditioning for 10 days at 25°C / 55% RH, the samples were ready for testing. Testing of the samples was also performed in a controlled environment chamber set at 25°C / 55% RH to minimize variability due to temperature or relative humidity. To perform the TCBC test, we started by opening the corresponding software. A ½ inch segment of the seal was peeled off from the side of the sample to expose the ITO-PET surface. On a computer with Windows® 10, we opened the TCBC resistivity program using Labview 2014 and the TCBC waveform program. The contact area of ​​the single pixel area used to measure the resistivity of the samples was determined to be 25 cm. 2 The voltage was set to 0.5 V. The range was set to 200 μA (also fitted to a model 6487 Electrometer). One alligator clip was connected to the ITO-PET of the seal resistivity sample. The other alligator clamp was connected to the first test pixel on the graphite backplane. Once the connections were set, the test was started. During the test, the following waveform was executed to pulse to a magnitude of 15 volts for a total of 26699 milliseconds, as shown in FIG. 8E. During this time, the current was measured as a function of time by the software program and electrometer. The software then calculated the resistance of the sample from the measured current and input voltage based on Ohm's law: R=(V / I), where V is the input voltage, I is the measured current, and R is the resistance. To calculate the final volume resistivity of the sample, the following equation was used: r=R / t, where R is the resistance from the test and t is the thickness of the seal film measured using a thickness gauge to complete the test.

[0136] D. Electrical Impedance Spectroscopy (EIS): Electrical impedance spectroscopy (EIS) was used to understand how the presence of a water-soluble ether (dipropylene glycol dimethyl ether) in the sealing film affects the electro-optical performance without increasing the volume resistivity of the film. EIS determined the interfacial resistivity between the sealing film and the electrophoretic medium (containing a non-polar solvent and charged yellow pigment particles).

[0137] The EIS results were used to calculate the distribution of relaxation times (DRT). Figure 9 shows a graph of gamma value versus relaxation time (tau) from the EIS data of the sealing film of the present invention (containing water-soluble ether) versus the control sealing film (not containing water-soluble ether) for two different electrophoretic media A and B. The different peaks of gamma value (tau) at different relaxation times correlate with different parallel resistor and capacitor (RC) elements in the electro-optical device containing the sealing film in contact with the electrophoretic medium. Each peak is the average of the relaxation times for all RC elements with similar relaxation times in the electro-optical device. The gamma value for each relaxation time is a measure of the resistance at the corresponding RC element. The relaxation time (tau) of 4 1 / sec most likely corresponds to the RC element at the sealing film-electrophoretic medium interface. As can be seen for both electrophoretic media A and B, the resistance at the interface of the sealing film and the electrophoretic medium is lower for the sealing film containing water-soluble ether (dipropylene glycol dimethyl ether). The lower interfacial resistance corresponds to improved electro-optical performance, as per the data in the table of examples.

[0138] E. Determination of the surface energy of the film.

[0139] The surface energy of the prepared sealing film (as described in B1 above) was measured using a drop shape analyzer supplied by Kruss GmbH. Using a syringe with a needle, a drop of deionized water with a size of 2.6 μL was placed on the top surface of the sealing film and the contact angle between the liquid (water) and the sealing film was measured. The measurement was repeated by replacing the water drop with a diiodomethane drop. The surface energy of the film was calculated by performing contact measurements using these two liquids of known surface energy. The contact angle measurement was repeated three times for each liquid (water and diiodomethane). The contact angle between the liquid and the top surface of the sealing film was measured using a high-resolution camera 5 seconds, 30 seconds, and 55 seconds after the drop was placed on the sample film. The total surface energy, as well as its polar and dispersive components, were then calculated for each data point using the method of Owens, Wendt, Rabel, and Kaelble (OWRK). The reported surface energies were the average of nine data points (3 drops x 3 scales).

[0140] F. Preparation of electro-optical devices.

[0141] An electro-optical device was prepared by filling a number of microcells with a mixture of electrically charged pigment particles (white, cyan, magenta, and yellow) in Isopar E. The white and yellow particles are negatively charged, and the cyan and magenta particles are positively charged. An aqueous sealing composition was then coated onto the openings of the microcells as described in B above. The device shown in FIG. 10 was constructed. The electro-optical device 1000 included, in order, a protective film 1001, an optically transparent first adhesive layer 1002, a substrate 1003, a light-transmitting conductive layer 10904, a primer layer 1005, a microcell layer 1006, a sealing film 1007, a second adhesive layer 1008, an ITO electrode layer 1009, and a glass layer 1010. A source of electric field 1011 electrically connected the light-transmitting conductive layer 1004 with the ITO electrode layer 1009. This source applied a waveform to drive the desired optical state. The first light transmitting layer 1002 had a thickness of approximately 25 μm. The substrate 903 had a thickness of approximately 100 μm. The primary layer 1005 had a thickness of approximately 0.4 μm. The microcell layer 1006 included a plurality of microcells. Each microcell had a bottom thickness of approximately 0.4 μm and a height of approximately 10 μm. The seal film 807 had a thickness of approximately 10 μm and the second adhesive layer had a thickness of approximately 4.5 μm.

[0142] G. Color Gamut Measurement.

[0143] The electro-optical device prepared by method F was electrically driven to produce eight optical states. The electrophoretic device was addressed using a sequence of electrical pulses (such sequences are referred to as "waveforms"). In the following description, the voltages used in the waveforms are those supplied to the rear electrode of the display, assuming that the electrode at the front (screen viewing) surface of the display is a common electrode for all pixels and is grounded. The test waveform includes a "dipole" sequence, as shown in FIG. 11. Each dipole is composed of two monopoles, each of which is a pulse of length t and magnitude V. The two monopoles in each dipole are of opposite polarity.

[0144] The voltages used in the test waveforms were + / -24V, + / -18V, + / -15V and + / -10V. Time was discretized into units of 11.74 milliseconds, called "frames." Each frame would correspond to one scan of a thin-film transistor array backplane refreshed at a frequency of 85Hz, although in the tests described the backplane was segmented and directly driven.

[0145] Two types of test waveforms were used to assess the electro-optical performance of the device. The waveform used in the first test was 18 frames in length, while the waveform used in the second test was 42 frames in length. In each case the waveform was injected with as many additional identical dipoles as would fit within the allowed number of frames. This is shown in Tables 1 and 2, corresponding to the 18 and 42 frame waveform types, respectively.

[0146] [Table 1]

[0147] [Table 2]

[0148] The length of the second monopole was the length of the dipole minus the length of the first monopole. It should be noted that "first" and "second" do not necessarily imply a particular time order of the monopoles that make up the dipole. Not all dipoles corresponding to these rules were used. To perform more reasonable length tests, only waveforms with (V2*t2) / (V1*t1)<2 were used.

[0149] Each waveform was preceded by a DC balance pulse (having an equal and opposite impulse to the particular test waveform) and a reset of the display to the white state. Each waveform was terminated by a 3 second ground.

[0150] The color states of the display (measured in CIELab L*, a*, and b* units) were recorded after a 3-second grounding period. The color gamut of the display was measured by computing the volume of a convex hull containing all colored states generated by a set of test waveforms. The eight color states produced were red, green, blue, yellow, cyan, magenta, white, and black (R, G, B, Y, C, M, W, and K). The color gamut was calculated using the DE 3 The color gamut is reported in units of color, and is larger in space than the optical gamut, indicating better electro-optical performance of the electro-optical device.

[0151] H. Determination of interfacial tension of polymers.

[0152] For a particular combination of polymers, the interfacial tension between polymer 1 and polymer 2 was calculated from the surface tension values ​​(determined by the method described in H above). Calculation of the interfacial tension between two components was performed by using the surface energy values ​​of each component and the following geometric equation:

number

[0153] Similarly, the interfacial tension between the seal film and the adhesive layer can be measured.Polyurethane-containing adhesive standards were formed with an aqueous dispersion of water-dispersible polyurethane.

[0154] I. Evaluation of the barrier properties of sealing films against non-polar fluids.

[0155] An aqueous dispersion was prepared by mixing 10 grams of poly(vinyl alcohol) homopolymer or 10 grams of poly(vinyl alcohol-co-ethylene) copolymer and 10 grams of polyurethane in 100 mL of water. The dispersion was used as the aqueous polymer composition to form the sealing film of device 1200 shown in FIG. 12. The sealing film was formed by the method described in B1 above. Device 1200 included, in order, substrate 1203, light-transmitting conductive layer 1204, primer layer 1205, microcell layer 1206, and sealing film 1207. The microcell contained an electrophoretic medium comprising white, black, and red pigment particles in Isopar E. Device 1200 was stored at 70° C. for at least 24 hours. After this period, the electro-optical device was inspected using an optical microscope for sagging of the sealing film caused by loss of the non-polar fluid of the electrophoretic medium. If the distance between the bottom of the inspected microcavity and the lowest point of the bottom surface of the sealing film is less than 85% of the distance between the bottom of the microcavity and the highest point of the bottom surface of the sealing film in the same microcell, the aqueous polymer composition is classified as "fail" for its barrier properties. Otherwise, i.e., if the distance between the bottom of the inspected microcell and the lowest point of the sealing film is 85% or greater than the distance between the bottom of the microcell and the highest point of the bottom surface of the sealing film in the inspected microcell, the sealing aqueous polymer composition is classified as "pass" for its barrier properties. For example, the aqueous polymer composition used to prepare the electro-optical device shown in FIG. 13C was classified as "pass" because the ratio of h2:h1 was 1 (no sagging), while the aqueous polymer composition used to prepare the electro-optical device shown in FIG. 13D was classified as "fail" because the ratio of h2:h1 was 35% (sagging level above 85%). Assessment of the barrier properties can also be performed qualitatively by observing the prepared electro-optical devices viewed from the observation side of the device with an optical microscope.A device containing a severely sagging seal film has a significantly different appearance (uniform vs. non-uniform surface) than a device containing a seal film with good barrier properties to non-polar fluids. For example, a microcell having an aqueous polymer composition corresponding to the seal film of FIG. 13C ("pass") appears uniform as shown in FIG. 13A, in contrast to a microcell having an aqueous polymer composition corresponding to the seal film of FIG. 13D ("fail"), which appears non-uniform as shown in FIG. 13B. Evaluation of various combinations of (1) poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer and (2) polyurethane are shown in Table 10. Polymer 1 is a poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer, and polymer 2 is a polyurethane. Details regarding the commercially available materials of polymer 1 and polymer 2 can be found in Table 11.

[0156] J. Determination of the content of water-soluble ethers in sealing films.

[0157] The content of water-soluble ether in the sealing film was determined by a combination of thermogravimetric analysis (TGA) and Karl Fischer (KF) moisture analysis. The total amount of water-soluble ether and moisture in the sealing film is determined by the following thermogravimetric analysis method. The moisture content in the sealing film is measured using the Karl Fischer method at 150°C. The content of water-soluble ether in the sealing film was then calculated by subtracting the moisture content (KF) from the total amount of water-soluble ether and moisture (TGA). The thermogravimetric analysis included (a) taring the sample holder, (b) placing the sample in the sample holder and weighing, (c) equilibrating the sample at 30°C, (d) heating the sample to 105°C at a heating rate of 50°C / min, (e) holding the sample at 105°C for 10 minutes to evaporate moisture and other volatile materials from the sample, (f) heating the sample to 215°C at a rate of 50°C / min, (g) holding the sample at 215°C for 10 minutes to evaporate water-soluble ethers, and (h) heating the sample to 650°C at a rate of 20°C / min to completely decompose the sample. The samples were kept under nitrogen gas during the thermogravimetric analysis. The total amount of moisture and water-soluble ethers was obtained by the weight loss of the sample from 40°C to 220°C using Trios software.

[0158] Evaluation results

[0159] Unless otherwise stated, the amount of ingredients in the disclosed compositions in the following table is provided as the weight percentage of the ingredient relative to the weight of the composition excluding water. To express the content of water carrier, the term QS (quantity sufficient) is used in some compositions. This term means that the content of water in the composition is the amount necessary to achieve and not exceed the total of 100% of the composition.

[0160] If any residual or absorbed water or moisture is present in the seal film, the disclosed contents of the ingredients of the seal film are calculated as the weight % of the ingredient relative to the weight excluding residual or absorbed water, unless otherwise stated.

[0161] The example compositions having numbers ending with the letter F correspond to seal film compositions, while the remaining example compositions correspond to aqueous seal compositions. The seal film composition examples correspond to the same example number (with the suffix F) as the aqueous seal composition used to prepare the seal film composition. Thus, Example 1F (seal film composition) was prepared from Example 1 (aqueous seal composition).

[0162] The content of water-soluble ether in the seal film of Example 19F was determined to be 8.6% by weight based on the weight of the seal film using the method described above in J. The content of water-soluble ether in the other seal film examples was calculated as 63% of the total water-soluble ether in the aqueous seal composition.

[0163] [Table 3A]

[0164] [Table 3B]

[0165] Tables 3A and 3B show that aqueous sealing compositions containing a water-soluble ether, e.g., dipropylene glycol dimethyl ether or tetraethylene glycol dimethyl ether, form sealing films with higher volume resistivities, as opposed to control aqueous sealing compositions not containing a water-soluble ether, by 10 9 The results show that the resulting seal film has a volume resistivity (TCBC) of less than 1.0 ohm.cm. This is shown by comparing Examples 1F-5F with Comparative Example 6F and Examples 7F-8F with Comparative Example 9F.

[0166] [Table 4A]

[0167] [Table 4B]

[0168] [Table 5A]

[0169] [Table 5B]

[0170] [Table 6A]

[0171] [Table 6B]

[0172] [Table 7A-1]

[0173] [Table 7A-2]

[0174] Tables 4A, 4B, 5A, 5B, 4A, 6B, 7A, and 7B show that the aqueous sealing compositions containing water-soluble ethers, such as dipropylene glycol dimethyl ether or tetraethylene glycol dimethyl ether, form sealing films with a larger color gamut than the control aqueous sealing compositions that do not contain the water-soluble ether. This is shown by comparing the examples of the present invention with the corresponding comparative examples. Improved electro-optical performance is consistently observed in the color gamuts measured at different temperatures (0°C and 25°C).

[0175] [Table 8A]

[0176] [Table 8B]

[0177] [Table 9A]

[0178] [Table 9B]

[0179] Tables 8A, 8B, 9A, and 9B show that the aqueous sealing compositions containing a water-soluble ether, e.g., dipropylene glycol dimethyl ether (Examples 18-19 and Example 21), form sealing films with interfacial tensions with the adhesive layer lower than 20 mN / m, in contrast to the aqueous sealing compositions not containing a water-soluble ether (Comparative Example 20 and Comparative Example 22).

[0180] [1] Poly(vinyl alcohol-co-ethylene) copolymer; Exceval® RS-1717 supplied by Kuraray;

[0181] [2] Polyurethane aqueous dispersion; L3838 aqueous dispersion supplied by Hauthaway as a 35% dispersion in water;

[0182] [3] Carbon black; Nerox® 3500 supplied by Orion Engineered Carbon;

[0183] [4] Polycarbodiimide (polyfunctional polycarbodiimide-aqueous solution); CARBODILITE® V-02-L2 supplied by Nisshinbo Chemical as a 40% solution in water;

[0184] [5] Hydrophobically modified alkali swellable acrylic emulsion; Solthix™ A-100 supplied by Lubrizol;

[0185] [6] Siloxane polyalkylene oxide copolymers; Silwet® L-7607 copolymer supplied by Momentive;

[0186] [7] Dipropylene glycol dimethyl ether; Proglyde® DMM supplied by Dow Chemical;

[0187] [8] Tetraethylene glycol dimethyl ether; supplied by Sigma Aldrich (CAS 143-24-8).

[0188] Table 10 includes surface energy data for various Polymer 1 species, which are water-soluble poly(vinyl alcohol) homopolymers or poly(vinyl alcohol-co-ethylene) copolymers, and Polymer 2 species, which are polyurethanes. Table 10 also includes the calculated interfacial evaluation of the barrier properties of the various layers and various polymer combinations. The methods for preparing the corresponding polymer layers used to evaluate the barrier properties are described in I above. Surface energy determinations (following the method described in E above) were performed by first preparing and conditioning a seal film from the corresponding aqueous composition containing only one of the polymers. The interfacial tension for each polymer combination was calculated from the surface energy data and the calculation method described in H above.

[0189] [Table 10-1] [Table 10-2] [Table 10-3]

[0190] [Table 11-1] [Table 11-2]

[0191] The interfacial tension data for polymer 1 and polymer 2 in Table 10 show that a sealing film comprising (a) a poly(vinyl alcohol) polymer or poly(vinyl alcohol-co-ethylene) copolymer having a degree of hydrolysis of 90% to 99.5% and an ethylene content of less than 10%, and (b) a polyurethane in an aqueous carrier, where the interfacial tension between the two polymers (a) and (b) is less than 2 mN / m, forms a sealing film having good barrier properties against non-polar fluids.

[0192] The data in Table 10 also show that sealing films made from aqueous sealing compositions comprising (a) a poly(vinyl alcohol) polymer or poly(vinyl alcohol-co-ethylene) copolymer having a degree of hydrolysis of 90% to 99.5% and an ethylene content of less than 10%, and (b) a polyurethane in an aqueous carrier, where the polar component of the polyurethane's surface energy is between 10 and 25 mN / m, form sealing films with good barrier properties to non-polar fluids.

[0193] Microscopic evaluation of the sealing films prepared by the four aqueous sealing compositions prepared by the method described in B1 above showed that there is a correlation between the uniformity of the film and the interfacial tension between the two polymers. The microscopic images in Table 12 and Figure 14 show that the lower interfacial tension provides a more uniform sealing film. The improved compatibility achieved by the combination of polymers with lower interfacial tension may explain the improved barrier properties of the corresponding layers.

[0194] [Table 12]

[0195] During further investigation, it was observed that aqueous sealing compositions containing more than 70% by weight of poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer, based on the weight of the aqueous sealing composition excluding water, formed sealing films that absorbed significant amounts of moisture from the environment, and this high moisture absorption negatively impacted the electro-optical performance of the display.

Claims

1. a water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer with a content of 15% to 60% by weight based on the weight of the seal film, said poly(vinyl alcohol) homopolymer having a degree of hydrolysis of 90% to 99.5%, said poly(vinyl alcohol-co-ethylene) copolymer having a degree of hydrolysis of 90% to 99.5% and an ethylene content of less than 10%; Polyurethane in an amount of 7% to 29% by weight based on the weight of the seal film; Carbon black in an amount of 5% to 70% by weight based on the weight of the seal film; A water-soluble ether having a content of 0.5% to 25% by weight based on the weight of the sealing film and a molecular weight of 75 to 5,000 Daltons, and optionally containing a hydroxyl group. Includes a sealing film.

2. 10. The seal film of claim 1, wherein the total surface energy of the seal film is less than 60 mN / m.

3. 2. The seal film of claim 1, wherein the interfacial tension between the water-soluble poly(vinyl alcohol) polymer or poly(vinyl alcohol-co-ethylene) copolymer and the polyurethane is less than 2 mN / m.

4. 2. The seal film of claim 1, wherein the carbon black has an oil absorption of less than 100 mL per 100 mg of carbon black as measured using the OAN method according to ASTM 2414.

5. The carbon black has a 70 mm adsorption capacity as measured using a nitrogen adsorption method according to ASTM D 6556. 2 13. The seal film of claim 1 having a total surface area of ​​less than 1 / g.

6. The water-soluble ether is represented by Formula I, Formula II, or Formula III 【Chemistry 5】 [In the formula, n is 1 to 145; R1 is a hydrogen, methyl or ethyl group; R2, R3, R4, R5, R6, and R7 are independently selected from the group consisting of hydrogen, a linear or branched alkyl group containing 1 carbon atom to 6 carbon atoms, phenyl, and a benzyl group; Formula I contains at least one ether functional group, Formula II includes at least one ether functional group, Formula III contains at least one ether functional group. The seal film of claim 1 , represented by:

7. The seal film according to claim 6, wherein n is 1 to 10.

8. The water-soluble ether may be ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-n-propyl ether, ethylene glycol monoisopropyl ether, ethylene glycol n-monobutyl ether, ethylene glycol monoisobutyl ether, ethylene glycol mono-t-butyl ether, ethylene glycol monobenzyl ether, ethylene glycol monophenyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol di-n-propyl ether, ethylene glycol diisopropyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol mono-n-propyl ether, diethylene glycol monoisopropyl ether, diethylene glycol n-monobutyl ether, diethylene glycol monoisobutyl ether, diethylene glycol mono-t-butyl ether, diethylene glycol monobenzyl ether, diethylene glycol monophenyl ether, diethylene glycol dimethyl ether, glycol diethyl ether, diethylene glycol ethyl methyl ether, diethylene glycol di-n-propyl ether, diethylene glycol diisopropyl ether, diethylene glycol di-n-butyl, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol mono-n-propyl ether, triethylene glycol monoisopropyl ether, triethylene glycol n-monobutyl ether, triethylene glycol monoisobutyl ether, triethylene glycol mono-t-butyl ether, triethylene glycol monobenzyl ether, triethylene glycol monophenyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol di-n-propyl ether, triethylene glycol diisopropyl ether, tetraethylene glycol monomethyl ether, tetraethylene glycol monoethyl ether, triethylene glycol monophenyl ether, tetraethylene glycol dimethyl ether, polyethylene glycol monomethyl ether,Polyethylene glycol monoethyl ether, polyethylene glycol monophenyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono-n-propyl ether, propylene glycol monoisopropyl ether, propylene glycol mono-n-butyl ether, propylene glycol monoisobutyl ether, propylene glycol monophenyl ether, propylene glycol dimethyl ether, propylene glycol diethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol mono-n-propyl ether, dipropylene glycol monoisopropyl ether, propyl ether, dipropylene glycol mono-n-butyl ether, dipropylene glycol monoisobutyl ether, dipropylene glycol dimethyl ether, dipropylene glycol diethyl ether, dipropylene glycol di-n-propyl ether, dipropylene glycol diisopropyl ether, tripropylene glycol monomethyl ether, tripropylene glycol monoethyl ether, tripropylene glycol mono-n-propyl ether, tripropylene glycol monoisopropyl ether, tripropylene glycol mono-n-butyl ether, and tripropylene glycol monoisobutyl ether.

9. 10. The seal film of claim 1 further comprising an organosilicone wetting agent.

10. 10 8 ~10 10 10. The seal film of claim 1 having a volume resistivity of 100 ohm.cm.

11. The seal film of claim 1 , wherein the polyurethane is an ester polyurethane, a polycarbonate polyurethane, or a combination thereof.

12. The seal film of claim 1, wherein the polyurethane polymer has a number average molecular weight of 1,000 to 2,000,000 Daltons.

13. 2. The seal film of claim 1, wherein the poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer has a number average molecular weight of 1,000 to 1,000,000 Daltons.

14. The seal film of claim 1, wherein the poly(vinyl alcohol) polymer or poly(vinyl alcohol-co-ethylene) copolymer has a degree of hydrolysis of 92% to 99%.

15. The seal film of claim 1, wherein the poly(vinyl alcohol-co-ethylene) copolymer has an ethylene content of less than 9%.

16. A conductive layer, a microcell layer including a plurality of microcells, each microcell including an aperture, each microcell including an electrophoretic medium, the electrophoretic medium including charged particles in a non-polar carrier; 13. The sealing film of claim 1 , spanning the opening of each microcell. An adhesive layer, and electrode layer 2. An electro-optical device comprising:

17. 17. The electro-optic device of claim 16, wherein the electrophoretic medium includes at least three types of charged pigment particles, one type of charged particles having a color selected from the group consisting of blue, green, red, cyan, magenta, and yellow.

18. a water-soluble poly(vinyl alcohol) homopolymer or poly(vinyl alcohol-co-ethylene) copolymer in a content of 14% to 55% by weight based on the weight of the aqueous seal composition excluding water, said poly(vinyl alcohol) homopolymer having a degree of hydrolysis of 90% to 99.5% and said poly(vinyl alcohol-co-ethylene) copolymer having a degree of hydrolysis of 90% to 99.5% and an ethylene content of less than 10%; Polyurethane in an amount of 6% to 27% by weight based on the weight of the aqueous sealing composition excluding water; Carbon black in an amount of 5% to 64% by weight based on the weight of the aqueous sealing composition excluding water; a water-soluble ether in an amount of 1.0% to 40% by weight based on the weight of the aqueous sealing composition excluding water, the water-soluble ether having a molecular weight of 75 to 5,000 daltons and optionally containing a hydroxyl group; Water content of 20% to 95% by weight based on the weight of the aqueous sealing composition The aqueous sealing composition comprises:

19. 19. The aqueous sealing composition according to claim 18, further comprising a crosslinking agent in an amount of 0.1% by weight to 8% by weight based on the weight of the aqueous sealing composition excluding water, the crosslinking agent being selected from the group consisting of polyisocyanate, polyfunctional polycarbodiimide, polyfunctional aziridine, silane coupling agent, boron / titanium / zirconium-based crosslinking agent, and melamine formaldehyde.

20. The aqueous sealing composition further comprises a rheology modifier in an amount of 0.05% to 5% by weight based on the weight of the sealing film rheology, -4 Viscosity at a shear rate of 1 / sec and 10 2 20. The aqueous sealing composition of claim 18, having a rheological profile exhibiting a 5 to 10,000 times decrease in viscosity between the viscosity at a shear rate of 1 / sec.

Citation Information

Patent Citations

  • Display medium and writing device

    JP2002196372A

  • Compositions and methods for sealing microcells

    JP2016535293A

  • Electrophoretic display device and electronic apparatus

    JP2017032666A

  • Polyhydroxy compositions for sealing electrophoretic displays - Patent Application 20070122999

    JP2019510994A

  • Electrophoretic displays with improved high temperature performance

    US20040120024A1